Transfer Film

By stacking a heat sealing layer and an inorganic vapor-deposited film on the support substrate and adding an anchor coating, the problem of insufficient gas barrier performance of paper-based materials is solved, high inter-layer adhesion and layered gas barrier laminate is achieved, which is suitable for packaging materials.

JP7627402B2Active Publication Date: 2025-02-06DAI NIPPON PRINTING CO LTD +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023509337
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-03-26
Filing Date
2022-03-25
Publication Date
2025-02-06
Estimated Expiration
2042-03-25

AI Technical Summary

Technical Problem

In the prior art, the gas barrier properties of paper-based materials are insufficient, and there are problems of poor stability and insufficient interlayer adhesion when preparing the gas barrier film layer, especially when using physical or chemical vapor deposition methods.

Method used

Using transfer film technology, a structure including a support substrate, a heat sealing layer, an inorganic vapor-deposited film and an optional anchoring coating is formed by sequentially stacking a heat sealing layer and an inorganic vapor-deposited film on the support substrate and an anchoring coating is added therebetween layers to improve interlayer adhesion.

Benefits of technology

It realizes high interlayer adhesion and prevents layered gas barrier laminate, which is suitable for packaging materials and improves the gas barrier performance and recyclability of packaging materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007627402000006
    Figure 0007627402000006
  • Figure 0007627402000007
    Figure 0007627402000007
  • Figure 0007627402000008
    Figure 0007627402000008
Patent Text Reader

Abstract

A transfer film (2) comprising a support substrate (50), a heat seal layer (40), and an inorganic vapor deposition film (30), in this order in the thickness direction, wherein the inorganic vapor deposition film (30) and the heat seal layer (40) are in contact, or the transfer film (2) further comprises an anchor coating layer (32) between the inorganic vapor deposition film (30) and the heat seal layer (40), and the inorganic vapor deposition film (30) and the anchor coating layer (32) are in contact.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a transfer film and a barrier laminate. [Background technology]

[0002] In recent years, environmental issues caused by microplastics have been receiving a lot of attention. In order to reduce the environmental impact of paper-based products, there is a demand to improve recyclability by making the products as entirely made of paper as possible.

[0003] Conventionally, packaging materials with high gas barrier properties have been used as packaging materials that suppress deterioration of the quality of contents (e.g., food, medical products, chemical products, and cosmetics) due to moisture or oxygen. Here, packaging materials with a paper base material have been attracting attention, taking into consideration the recycling or incineration of used packaging materials. However, paper base materials generally have insufficient gas barrier properties. Therefore, in order to improve the gas barrier properties of packaging materials with a paper base material, coating the paper base material with a resin or laminating a resin film having an inorganic vapor deposition film on the paper base material has been considered.

[0004] Patent Document 1 discloses a laminate in which a thin gas barrier layer formed by plasma polymerization is laminated on a substrate made of paper or pulp mold having a surface with a filler layer made of a polycondensate of polysaccharide and silicon compound. In Patent Document 1, a substrate made of paper or pulp mold is placed in a plasma polymerization apparatus when forming a thin gas barrier layer, so that paper powder or pulp powder generated from the paper or pulp mold tends to prevent the inside of the plasma polymerization apparatus from being reduced in pressure to a level suitable for plasma polymerization. Therefore, it is difficult to form a thin film layer with stable gas barrier properties, and the adhesion between the filler layer and the thin film layer tends to be insufficient, and the gas barrier properties tend to be unstable. Patent Document 1 relates to a chemical vapor deposition method for forming a thin gas barrier layer, but physical vapor deposition also has similar problems. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Patent No. 4622201 Summary of the Invention [Problem to be solved by the invention]

[0006] It is desired to provide a barrier laminate having excellent interlayer adhesion, not limited to a paper substrate, and having a substrate that is difficult to directly vapor-deposit. In addition, a packaging material usually has a heat seal layer to seal the packaging material. Therefore, a barrier laminate such as a barrier paper that is suitably used for packaging material applications preferably has a heat seal layer.

[0007] An object of the present disclosure is to provide a barrier laminate including a substrate, an inorganic vapor deposition film, and a heat seal layer, the barrier laminate having excellent interlayer adhesion and suppressing interlayer delamination. An object of the present disclosure is to provide a transfer film that can be suitably used in the production of such a barrier laminate. [Means for solving the problem]

[0008] The transfer film of the present disclosure comprises a supporting substrate, a heat seal layer, and an inorganic vapor deposition film in this order in the thickness direction, with the inorganic vapor deposition film and the heat seal layer in contact, or the transfer film further comprises an anchor coat layer between the inorganic vapor deposition film and the heat seal layer, with the inorganic vapor deposition film and the anchor coat layer in contact.

[0009] In one embodiment, the barrier laminate of the present disclosure comprises a substrate, an adhesive layer, an inorganic vapor deposition film, and a heat seal layer in this order in the thickness direction, with the inorganic vapor deposition film and the heat seal layer being in contact with each other, or the barrier laminate further comprises an anchor coat layer between the inorganic vapor deposition film and the heat seal layer, with the inorganic vapor deposition film and the anchor coat layer being in contact with each other.

[0010] In one embodiment, the barrier laminate of the present disclosure comprises a substrate, an adhesive layer, an inorganic vapor deposition film, and a heat seal layer in this order in the thickness direction, and does not comprise a release layer between the inorganic vapor deposition film and the heat seal layer. Effect of the Invention

[0011] According to the present disclosure, it is possible to provide a barrier laminate including a substrate, an inorganic vapor deposition film, and a heat seal layer, the barrier laminate having excellent interlayer adhesion and suppressing interlayer delamination. According to the present disclosure, it is possible to provide a transfer film that can be suitably used in the production of such a barrier laminate. [Brief description of the drawings]

[0012]

Figure 1

Figure 2

Figure 3

Figure 4

Figure 5

Figure 6

[0013] Hereinafter, embodiments of the present disclosure will be described with reference to the drawings, etc. The present disclosure can be implemented in many different forms, and should not be construed as being limited to the description of the embodiments exemplified below.

[0014] In order to clarify the explanation, the drawings may be schematic in terms of the width, thickness, angle, shape, etc. of each part compared to the actual form. However, the drawings are merely examples and do not limit the interpretation of the present disclosure. In this specification and each figure, elements similar to those described with respect to the previous figures may be given the same reference numerals, and detailed explanations may be omitted as appropriate. For convenience of explanation, the words "upper" or "lower" may be used in the explanation, but the up-down direction may be reversed. The same applies to the left-right direction.

[0015] In the following description, each component (for example, additives, resin components such as various resins, colorants, and curing agents) may be used in one or more types.

[0016] [Transfer film] The transfer film of the present disclosure includes a support substrate, a heat seal layer, and an inorganic vapor deposition film in this order in the thickness direction. The transfer film may further include an anchor coat layer between the heat seal layer and the inorganic vapor deposition film. The heat seal layer, and optionally the anchor coat layer and the inorganic vapor deposition film constitute a transfer layer. In one embodiment, the transfer film and the transfer layer may further include a functional layer such as a protective layer.

[0017] That is, the transfer film of the present disclosure includes a support substrate and a transfer layer provided on the support substrate, and the transfer layer includes a heat seal layer and an inorganic vapor deposition film in this order in the thickness direction. In one embodiment, the transfer layer may further include an anchor coat layer between the heat seal layer and the inorganic vapor deposition film. The heat seal layer is in contact with the support substrate and is provided so as to be peelable from the support substrate.

[0018] Here, in the transfer layer, the inorganic vapor deposition film and the heat seal layer (or the anchor coat layer if an anchor coat layer is provided) are in contact with each other, or the transfer layer does not have a release layer between the inorganic vapor deposition film and the heat seal layer.

[0019] In one embodiment, the transfer film includes a protective layer on the inorganic vapor deposition film. In one embodiment, when the inorganic vapor deposition film is made of a metal oxide such as aluminum oxide or silicon oxide, the transfer film has a barrier coat layer on the inorganic vapor deposition film.

[0020] The support substrate as the transfer substrate, that is, the transfer film, may be a sheet film or a continuous film wound in a roll.

[0021] One embodiment of the transfer film of the present disclosure is shown in Fig. 1. The transfer film 2 in Fig. 1 includes a support substrate 50, a heat seal layer 40, and an inorganic vapor deposition film 30 in this order in the thickness direction.

[0022] Another embodiment of the transfer film of the present disclosure is shown in Fig. 2. The transfer film 2 in Fig. 2 includes a support substrate 50, a heat seal layer 40, an anchor coat layer 32, and an inorganic vapor deposition film 30 in this order in the thickness direction.

[0023] <Supporting base material> The transfer film of the present disclosure includes a supporting substrate as a transfer substrate. The support substrate is preferably a film made of resin (hereinafter also referred to as "resin film"). Examples of the resin include polyesters such as polyethylene terephthalate (PET) and polybutylene terephthalate (PBT); various nylons, particularly polyamides such as aromatic polyamides such as nylon MXD6; vinyl resins such as ethylene-vinyl acetate copolymers, ethylene-vinyl alcohol copolymers and polyvinyl alcohol; polyolefins such as polyethylene, polypropylene, polybutene and cyclic polyolefins; styrene-based resins such as styrene homopolymers, acrylonitrile-styrene copolymers (AS resins), and acrylonitrile-butadiene-styrene copolymers (ABS resins); (meth)acrylic resins, polycarbonates, polyimides, diaryl phthalate resins, silicone-based resins, polysulfone-based resins, polyphenylene sulfide-based resins, polyethersulfone-based resins, polyurethanes, cellulose-based resins, and fluorine-based resins.

[0024] The resin film may be composed of one layer, or may be composed of two or more layers of the same or different compositions. The resin film may be an unstretched film, or a stretched film such as a uniaxially stretched film or a biaxially stretched film.

[0025] The thickness of the supporting substrate is preferably 5 μm or more, more preferably 8 μm or more, and even more preferably 10 μm or more, and is preferably 200 μm or less, more preferably 100 μm or less, and even more preferably 80 μm or less.

[0026] The supporting substrate preferably has a property that allows a heat seal layer to be formed on the substrate and allows the substrate to be easily peeled from the heat seal layer in a peeling step. From this viewpoint, among the resin films, polyester films and polyamide films are preferred, polyester films are more preferred, and polyethylene terephthalate films are even more preferred.

[0027] The supporting substrate has excellent mechanical, physical and chemical properties, particularly strength and heat resistance, so that it can withstand the process of forming an inorganic vapor deposition film. A polyethylene terephthalate film is also preferable from this viewpoint.

[0028] It is preferable that the resin film is not subjected to a known easy-adhesion treatment on the surface in contact with the heat seal layer, and is also preferable that the resin film is not provided with a known easy-adhesion layer on the surface in contact with the heat seal layer. With such a configuration, for example, the peelability between the support substrate and the heat seal layer in the peeling step can be improved.

[0029] <Heat seal layer> The transfer film of the present disclosure includes a heat seal layer. The heat seal layer functions as a heat sealable sealant layer when a barrier laminate such as barrier paper is used as a packaging material. The heat seal layer also functions as a release layer from a support substrate when a barrier laminate such as barrier paper is produced by a transfer method described later.

[0030] The heat seal layer is a layer having heat sealability, specifically, a layer that can be adhered to an object to be adhered by heating and pressing, or a layer that can be fused and adhered to itself by heating and pressing. Note that the transfer film of the present disclosure may also be used for purposes that do not require heat sealing.

[0031] In the transfer film of the present disclosure, the heat seal layer is preferably in contact with the supporting substrate. With this configuration, the supporting substrate can be easily peeled off from the heat seal layer. For example, since the heat seal layer is unlikely to remain on the supporting substrate after peeling, the supporting substrate can be easily recycled or reused.

[0032] The heat seal layer that can be peeled off from the supporting substrate can be formed, for example, using a thermoplastic resin. Examples of the thermoplastic resin include an olefin-based polymer and a (meth)acrylic resin. Among these, an olefin-based polymer is preferable.

[0033] In one embodiment, the heat seal layer contains an olefin-based polymer. By configuring in this way, for example, a heat seal layer excellent in heat sealability and peelability can be obtained, and a barrier laminate for packaging materials having sufficient rigidity, strength, and heat resistance and excellent recyclability can be obtained.

[0034] Examples of the olefin polymer include ethylene polymers and propylene polymers. Among these, ethylene polymers are preferred from the viewpoint of the balance between heat sealability and peelability.

[0035] Examples of ethylene polymers include high density polyethylene, medium density polyethylene, low density polyethylene, linear low density polyethylene, and very low density polyethylene, and from the viewpoint of heat sealability, low density polyethylene, linear low density polyethylene, and very low density polyethylene are preferred. From the viewpoint of reducing the environmental load, biomass-derived polyethylene and / or recycled polyethylene may be used.

[0036] The density of the high density polyethylene is preferably 0.945 g / cm 3 The upper density limit of high density polyethylene is, for example, 0.965 g / cm 3 The density of the medium density polyethylene is preferably 0.925 g / cm 3 Exceeds 0.945g / cm 3 The density of the low density polyethylene is preferably 0.900 g / cm 3 Exceeds 0.925g / cm 3 The density of the linear low density polyethylene is preferably 0.900 g / cm 3 Exceeds 0.925g / cm 3 The density of the very low density polyethylene is preferably 0.900 g / cm 3 The lower limit of the density of the very low density polyethylene is, for example, 0.860 g / cm 3 The density of polyethylene is measured in accordance with JIS K7112 (1999).

[0037] Examples of ethylene-based polymers include ethylene-(meth)acrylic acid ester copolymers such as ethylene-vinyl alcohol copolymers, ethylene-vinyl acetate copolymers, modified ethylene-vinyl acetate copolymers, ethylene-maleic anhydride copolymers, ethylene-(meth)acrylic acid copolymers, and ethylene-(meth)acrylic acid alkyl ester copolymers (e.g., ethylene-ethyl acrylate copolymers).

[0038] Examples of the propylene-based polymer include propylene homopolymer, propylene random copolymer, and propylene block copolymer. Propylene homopolymer is a polymer of propylene only. Propylene random copolymer is a random copolymer of propylene and an ethylenically unsaturated monomer other than propylene (e.g., α-olefin such as ethylene, 1-butene, 4-methyl-1-pentene, etc.). Propylene block copolymer is a copolymer having a polymer block of propylene and a polymer block of an ethylenically unsaturated monomer other than propylene (e.g., α-olefin such as ethylene, 1-butene, 4-methyl-1-pentene, etc.). From the viewpoint of reducing the environmental load, biomass-derived polypropylene and / or recycled polypropylene may be used. Propylene-maleic anhydride copolymer is also included as a propylene-based polymer.

[0039] The barrier laminate of the present disclosure is preferably produced by a transfer method, as described below. In the transfer method, a heat seal layer is formed on a supporting substrate, an inorganic vapor deposition film is further formed on the heat seal layer, and then the heat seal layer and the inorganic vapor deposition film are transferred onto a substrate such as a paper substrate. Therefore, it is preferable to form the heat seal layer using a coating liquid that can form a coating film on the supporting substrate and has excellent peelability from the supporting substrate as well as heat sealability.

[0040] Such a heat seal layer is preferably formed using a coating liquid for a heat seal layer containing an ionomer of an olefin polymer. An ionomer is a general term for synthetic resins in which polymers are aggregated by utilizing the cohesive force of metal ions.

[0041] Examples of the metal ion include alkali metal ions and alkaline earth metal ions, and specific examples include sodium, potassium, calcium, magnesium, and zinc ions.

[0042] Examples of ionomers of olefin-based polymers include metal salts of olefin-unsaturated carboxylic acid copolymers, metal salts of olefin-(meth)acrylic copolymers, metal salts of olefin-urethane copolymers, and metal salts of olefin-fluorine-based polymer copolymers.

[0043] Examples of the olefin include α-olefins having 2 to 20 carbon atoms, such as ethylene, propylene, 1-butene, 1-pentene, 1-hexene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, 1-eicosene, 3-methyl-1-butene, 4-methyl-1-pentene, and 6-methyl-1-heptene. Among these, ethylene and propylene are preferred, and ethylene is more preferred.

[0044] Examples of the unsaturated carboxylic acid include unsaturated monocarboxylic acids such as (meth)acrylic acid, crotonic acid, and β-carboxyethyl (meth)acrylate; and unsaturated dicarboxylic acids such as maleic acid, itaconic acid, fumaric acid, and citraconic acid.

[0045] Among the above ionomers, ionomers of ethylene-based polymers are preferred, metal salts of ethylene-(meth)acrylic acid copolymers, metal salts of ethylene-(meth)acrylic copolymers, metal salts of ethylene-urethane copolymers, and metal salts of ethylene-fluorine-based polymer copolymers are more preferred, and metal salts of ethylene-(meth)acrylic acid copolymers are even more preferred.

[0046] The content of the olefin polymer in the heat seal layer is preferably 80% by mass or more, more preferably 90% by mass or more, and even more preferably 95% by mass or more, which can further improve the heat sealability of the barrier laminate.

[0047] The heat seal layer may contain a rubber-based material together with the thermoplastic resin. Examples of the rubber-based material include thermoplastic rubber, natural rubber, butyl rubber, nitrile rubber, and chloroprene rubber. The rubber-based material may be used, for example, by mixing with the thermoplastic resin.

[0048] The heat seal layer is usually a layer that is not stretched. For example, the heat seal layer can be formed by applying a coating liquid for the heat seal layer containing an olefin polymer onto a supporting substrate and drying it, or by melt-extruding a resin composition containing an olefin polymer onto a supporting substrate. For the reasons described above, the heat seal layer is preferably a cast-coated layer formed using a coating liquid containing an olefin polymer.

[0049] Examples of the solvent for the heat seal layer coating liquid include water; alcohol solvents such as methanol, ethanol, 2-propanol, and 1-butanol; ketone solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone; glycol solvents such as ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, propylene glycol monomethyl ether, ethylene glycol monoethyl ether acetate, and propylene glycol monomethyl ether acetate; ester solvents such as methyl acetate, ethyl acetate, and butyl acetate; hydrocarbon solvents such as n-hexane, cyclohexane, benzene, toluene, and xylene; halogenated hydrocarbon solvents such as methylene chloride and chloroform; ether solvents such as dioxolane and tetrahydrofuran; nitrogen-containing solvents such as acetonitrile and N,N-dimethylformamide; and sulfur-containing solvents such as dimethyl sulfoxide.

[0050] In preparing the coating liquid for the heat seal layer, it is preferable to use an emulsion of an ionomer of an olefin polymer, more preferably a self-emulsifying emulsion, and even more preferably a self-emulsifying emulsion of a metal salt of an ethylene-(meth)acrylic acid copolymer. Such a coating liquid can, for example, satisfactorily form a coating film on a supporting substrate, and can form a coating film having excellent peelability from the supporting substrate, and the coating film is also excellent in heat sealability.

[0051] It is preferable to use a water-based ionomer emulsion as the emulsion. Such an emulsion allows the coating weight to be controlled to a relatively low level, and since there is no VOC emission, it is possible to obtain a packaging material with a small environmental impact.

[0052] The coating liquid for the heat seal layer may contain additives, such as a viscosity modifier, an antifoaming agent, a surfactant, a leveling agent, a lubricant, an antioxidant, an ultraviolet absorber, a light stabilizer, a filler, a reinforcing agent, an antistatic agent, a pigment, and a dye.

[0053] The thickness of the heat seal layer is preferably 1 μm or more, more preferably 3 μm or more, and preferably 25 μm or less, more preferably 15 μm or less. In one embodiment, the thickness of the heat seal layer is 5 μm or more and 25 μm or less. The thickness of the heat seal layer is preferably changed appropriately depending on the strength of the heat seal layer, the processability of the transfer film, and the mass of the contents filled in the packaging material produced using the barrier laminate of the present disclosure.

[0054] The indentation hardness of the heat seal layer is preferably 0.15 GPa or less, more preferably 0.10 GPa or less, and further preferably 0.08 GPa or less, and the lower limit may be, for example, 0.01 GPa or 0.02 GPa. When the indentation hardness is 0.15 GPa or less, for example, the bending resistance and gas barrier property of the barrier laminate tend to be further improved.

[0055] The composite elastic modulus of the heat seal layer is preferably 2.0 GPa or less, more preferably 1.5 GPa or less, and further preferably 1.0 GPa or less, and the lower limit may be, for example, 0.1 GPa or 0.2 GPa. When the composite elastic modulus is 2.0 GPa or less, for example, the bending resistance and gas barrier property of the barrier laminate tend to be further improved.

[0056] In the present disclosure, the indentation hardness and composite modulus of the heat seal layer can be adjusted, for example, by appropriately selecting the components contained in the heat seal layer.

[0057] In the present disclosure, the indentation hardness and composite modulus of the heat seal layer are measured by the nanoindentation method. Specifically, the indentation hardness and composite modulus are measured using a nanoindenter with the cross section of the heat seal layer of the transfer film as the measurement surface. The cross section is obtained by cutting the transfer film in the thickness direction perpendicular to the main surface. The location where the indenter is pressed is near the center in the thickness direction of the heat seal layer among the parts where the cross section of the heat seal layer is exposed. The measurement conditions are as follows. A Berkovich indenter (triangular pyramid indenter) is used as the indenter of the nanoindenter. The indenter is pressed into the heat seal layer from the cross section of the heat seal layer to a depth of 100 nm over 10 seconds, held in that state for 5 seconds, and then unloaded over 10 seconds, and the maximum load P max , contact projection area A at maximum depth p and load-displacement curves are obtained. From the load-displacement curves obtained, P max / A p The indentation hardness is calculated using the formula above, and the composite elastic modulus is calculated using the following formula (1).

[0058]

number

[0059] The measurements are performed at room temperature (23°C). Measurements are performed at 10 or more points on the same cross section, and the indentation hardness and composite modulus are reported as the arithmetic mean values ​​of the 10 points measured with good reproducibility. Details of the measurement conditions are described in the Examples section.

[0060] <Anchor coat layer> The transfer film of the present disclosure may further include an anchor coat layer between the heat seal layer and the inorganic vapor deposition film. By providing the anchor coat layer, the adhesion between the heat seal layer and the inorganic vapor deposition film can be increased, and the occurrence of peeling between these layers can be suppressed. For example, the anchor coat layer is in contact with the inorganic vapor deposition film on one side and in contact with the heat seal layer on the other side.

[0061] In one embodiment, the anchor coat layer contains a resin component. Examples of the resin component include thermoplastic resins such as polyolefins (e.g., polyethylene and polypropylene), vinyl resins, styrene-based resins, (meth)acrylic resins, polyesters, polyurethanes, and polyamides; and cured products of thermosetting resins such as phenolic resins, melamine resins, epoxy resins, alkyd resins, thermosetting (meth)acrylic resins, unsaturated polyesters, and thermosetting polyurethanes. When using a thermosetting resin, it is preferable to use a curing agent such as an amine compound, a phenolic compound, an isocyanate compound, or a carboxylic acid compound in combination. For example, polyester is preferable as the resin component from the viewpoint of adhesion.

[0062] Examples of polyesters include polymers synthesized by polycondensation of an acid component such as a polycarboxylic acid, its ester, or its acid anhydride with a polyhydric alcohol, lactone ring-opening polymers, polyhydroxycarboxylic acid polymers, urea-modified polyesters, and urethane-modified polyesters. Urethane-modified polyesters are polyesters having a urethane bond.

[0063] The urethane-modified polyester is, for example, a resin in which two or more polyesters are bonded together by a structural unit derived from a polyisocyanate. Such a resin can be obtained, for example, by reacting a terminal hydroxyl group of a polyester with an isocyanate group of a polyisocyanate.

[0064] The glass transition temperature (Tg) of the urethane-modified polyester may be 50° C. or higher, 60° C. or higher, or 70° C. or higher, and may be 120° C. or lower, or 110° C. or lower. Tg is the midpoint glass transition temperature obtained by differential scanning calorimetry (DSC) in accordance with JIS K7121.

[0065] The hydroxyl value of the urethane-modified polyester may be, for example, 1 mgKOH / g or more, 3 mgKOH / g or more, 5 mgKOH / g or more, 90 mgKOH / g or less, or 70 mgKOH / g or less. The hydroxyl value is expressed as the number of mg of potassium hydroxide required to neutralize the acetic acid bonded to the hydroxyl group when 1 g of the sample is acetylated. The hydroxyl value is determined in accordance with JIS K0070-1992.

[0066] The number average molecular weight (Mn) of the urethane-modified polyester may be 500 or more, 1,000 or more, or 50,000 or less, 30,000 or less, or 10,000 or less. Mn is measured by gel permeation chromatography (GPC) in accordance with JIS K7252-1 using polystyrene as a standard substance.

[0067] The urethane-modified polyester can be obtained, for example, by reacting a polyester polyol with a polyisocyanate. The urethane-modified polyester can be obtained, for example, by reacting a polyester polyol with a polyisocyanate in a ratio of excess hydroxyl groups relative to isocyanate groups, and preferably has two or more hydroxyl groups in one molecule. The reaction conditions of a normal urethane reaction can be widely applied to the reaction of the polyester polyol with the polyisocyanate.

[0068] The polyester polyol is a resin having two or more hydroxyl groups in one molecule, which is obtained by esterification of an acid component such as a polycarboxylic acid, its ester, or its acid anhydride with a polyhydric alcohol. The polyester polyol may be a polyester obtained by a ring-opening reaction of caprolactone.

[0069] Examples of polycarboxylic acids include aliphatic polycarboxylic acids such as malonic acid, succinic acid, glutaric acid, adipic acid, sebacic acid, azelaic acid, and dodecanedicarboxylic acid; aromatic polycarboxylic acids such as phthalic acid, isophthalic acid, terephthalic acid, trimellitic acid, and pyromellitic acid; and aliphatic polycarboxylic acids such as butanetricarboxylic acid, tricarballylic acid, and citric acid.

[0070] Examples of polyhydric alcohols include compounds having two or more hydroxyl groups in one molecule, such as dihydric alcohols such as aliphatic glycols, and polyhydric alcohols having three or more hydric groups. Examples of dihydric alcohols include ethylene glycol, diethylene glycol, 1,2-propanediol, 1,3-propanediol, 2-methyl-1,3-propanediol, 2,2-dimethyl-1,3-propanediol, 2,2-diethyl-1,3-propanediol, 1,2-butanediol, 1,3-butanediol, 1,4-butanediol, 1,5-pentanediol, 1,5-hexanediol, 1,6-hexanediol, 3-methyl-1,5-pentanediol, 2-ethyl-1,3-hexanediol, and 2,2,4-trimethyl-1,3-pentanediol. Examples of trihydric or higher polyhydric alcohols include aliphatic glycols, glycerin, trimethylolpropane, trimethylolethane, and pentaerythritol.

[0071] Examples of polyisocyanates include compounds having two or more isocyanate groups in one molecule. Specific examples of polyisocyanates include aliphatic diisocyanates such as hexamethylene diisocyanate, trimethylhexamethylene diisocyanate, lysine diisocyanate, and trimethylene diisocyanate; alicyclic diisocyanates such as isophorone diisocyanate, methylene bis(cyclohexyl isocyanate), and cyclohexane diisocyanate; and aromatic diisocyanates such as xylylene diisocyanate, tolylene diisocyanate, diphenylmethane diisocyanate, naphthalene diisocyanate, and biphenylene diisocyanate.

[0072] The urethane-modified polyester can also be obtained by simultaneously reacting an acid component such as a polycarboxylic acid, an ester thereof, or an acid anhydride thereof with a polyhydric alcohol and a polyisocyanate.

[0073] In one embodiment, the anchor coat layer may contain, as a resin component, a cured resin formed from a resin having a reactive functional group and a curing agent. Examples of the reactive functional group include a hydroxyl group, a carboxyl group, and an amino group. Examples of the resin having a reactive functional group include a urethane-modified polyester.

[0074] Examples of the curing agent include isocyanate compounds such as aromatic isocyanate compounds and aliphatic isocyanate compounds. Specific examples of the curing agent include aromatic isocyanate compounds such as tolylene diisocyanate (TDI-based isocyanate) and xylylene diisocyanate (XDI-based isocyanate); aliphatic isocyanate compounds such as hexamethylene diisocyanate (HDI-based isocyanate) and isophorone diisocyanate (IPDI-based isocyanate); modified products of these isocyanate compounds, and polyfunctionalized dimers, adducts, allophanates, trimers, carbodiimide adducts, biuret bodies, and polymers thereof and polymers to which polyhydric alcohols are added. As the curing agent, from the viewpoint of adhesion between the heat seal layer and the inorganic vapor deposition film, aromatic isocyanate compounds are preferred, and xylylene diisocyanate (XDI) is more preferred.

[0075] The amount of the curing agent used may be 10 parts by mass or more, 20 parts by mass or more, 200 parts by mass or less, or 150 parts by mass or less, relative to 100 parts by mass of the resin having a reactive functional group, which can further improve the adhesive strength between the heat seal layer and the inorganic vapor deposition film, for example.

[0076] The content of the resin component in the anchor coat layer may be 30% by mass or more, 50% by mass or more, 60% by mass or more, 80% by mass or more, 90% by mass or more, or 95% by mass or more. The resin component also includes the above-mentioned cured resin.

[0077] The anchor coat layer may contain additives, such as lubricants, antioxidants, ultraviolet absorbers, light stabilizers, fillers, reinforcing agents, antistatic agents, pigments, dyes, and silane coupling agents.

[0078] The anchor coat layer may further contain a compound having a glucose ring. Examples of the compound having a glucose ring include polysaccharides such as cellulose and pullulan and derivatives thereof. Examples of the derivative include methylated products, nitrated products, acetylated products, carboxymethylated products and cyanoethylated products. Examples of the derivative include cellulose acetate butyrate, cellulose acetate and methylcellulose; and compounds having a nitro group and a glucose ring such as nitrocellulose.

[0079] By adding a compound having a glucose ring to the anchor coat layer, for example, the above-mentioned adhesion can be further improved. Also, by adding a compound having a glucose ring to the anchor coat layer, the heat resistance of the anchor coat layer can be improved, deterioration of the anchor coat layer due to heat when forming an inorganic vapor deposition film on the anchor coat layer can be suppressed, and therefore the formed inorganic vapor deposition film can easily exhibit the desired gas barrier properties.

[0080] The content of the compound having a glucose ring in the anchor coat layer may be 5 parts by mass or more, 10 parts by mass or more, 20 parts by mass or more, 200 parts by mass or less, or 100 parts by mass or less, relative to 100 parts by mass of the resin component. When the content of the compound having a glucose ring is 20 parts by mass or more and 100 parts by mass or less, for example, adhesion and gas barrier properties can be further improved.

[0081] NO measured using time-of-flight secondary ion mass spectrometry (TOF-SIMS) in the anchor coat layer 2 - In one embodiment, the normalized intensity of the ions may be 0.5 or more, 1.0 or more, or 2.0 or more, but is preferably 3.0 or more, more preferably 3.2 or more, and even more preferably 3.5 or more. 2 - In one embodiment, the normalized intensity of the ion may be 5.0 or less, or 4.5 or less, preferably 4.2 or less, and more preferably 4.0 or less. 2- When the normalized ion intensity is 3.0 or more, the gas barrier properties and the appearance of the anchor coat layer tend to be more excellent. 2 - When the normalized ion intensity is 4.2 or less, the gas barrier properties and the adhesion between the anchor coat layer and the inorganic vapor deposition film tend to be superior.

[0082] NO 2 - The normalized intensity of the NO ion is calculated as follows: 2 - The detection intensity of the ion (mass number 45.992) is - The NO ion (mass number 26.002) was divided by the detection intensity and normalized by multiplying by 100,000. 2 - The common logarithm of the average detection intensity after normalization of ions is the NO 2 - The normalized ion intensity is defined as the intensity of the ions. Here, the central region of the anchor coat layer means a region near the center of the anchor coat layer, which has a thickness of 50% of the thickness of the anchor coat layer.

[0083] NO 2 - Normalized intensity of ion = log 10 {(NO 2 - Ion detection intensity / CN - ion detection intensity) × 100000}

[0084] The intensity of each ion is measured as follows. Using a time-of-flight secondary ion mass spectrometer (TOF.SIMS5, manufactured by ION TOF), soft etching is repeated at a constant speed from the outside of the transfer film using a Cs (cesium) ion gun to detect ions in each layer. Specific measurement conditions are described in the Examples section.

[0085] The thickness of the anchor coat layer is measured as follows. In the graph before normalization obtained by TOF-SIMS measurement, the position where the intensity of the ions derived from the inorganic vapor deposition film is 50% of the maximum intensity of the ions derived from the inorganic vapor deposition film is defined as the interface between the inorganic vapor deposition film and the anchor coat layer. For example, in the case of a silica vapor deposition film, the ions derived from the inorganic vapor deposition film are SiO 2 (mass number 59.96). In the graph before normalization obtained by TOF-SIMS measurement, CN - The ionic strength is CN - The position where the ion intensity is 50% of the maximum is determined as the interface between the anchor coat layer and the heat seal layer. The distance in the thickness direction between the above two interfaces is defined as the thickness of the anchor coat layer.

[0086] In one embodiment, the transition point of the anchor coat layer may be 70°C or more and 140°C or less. The transition point is preferably 90°C or more, more preferably 95°C or more, even more preferably 100°C or more, and particularly preferably 105°C or more. The transition point may be, for example, 135°C or less, 130°C or less, 125°C or less, or 120°C or less. When the transition point is 90°C or more, the gas barrier property tends to be more excellent. When the transition point is 125°C or less, the gas barrier property tends to be more excellent.

[0087] The transition point of the anchor coat layer is a value measured by local thermal analysis using a thermal probe. In the local thermal analysis using a thermal probe, the thermal probe is placed in contact with the cross section of the anchor coat layer, and the displacement of the thermal probe in the normal direction of the cross section of the anchor coat layer from before heating is measured while increasing the temperature, to obtain a thermal expansion curve.

[0088] The cross section is obtained by cutting the transfer film in the thickness direction perpendicular to the main surface. The location where the thermal probe comes into contact is near the center in the thickness direction of the anchor coat layer among the exposed parts of the cross section of the anchor coat layer. Measurements are performed at five or more points on the same cross section, and the transition point is recorded as the arithmetic average value of the five points measured with good reproducibility.

[0089] In local thermal analysis, the resin contained in the anchor coat layer expands due to heating, pushing up the thermal probe. The slope of the thermal expansion curve (displacement / temperature) changes due to structural transitions of the resin in the anchor coat layer. When the structural transition of the resin in the anchor coat layer changes, particularly from expansion to softening, the tip of the thermal probe penetrates into the resin, causing the thermal probe to descend. The point where the displacement of the thermal probe changes from rising to falling corresponds to the peak of the thermal expansion curve, and is called the softening point. The transition point of the anchor coat layer can be obtained by reading the temperature at the peak of the thermal expansion curve.

[0090] A "shoulder peak" may appear on a thermal expansion curve as the slope (displacement / temperature) of the thermal expansion curve changes. A "shoulder peak" is defined as a point where the slope of the thermal expansion curve (displacement / temperature) changes and the slope of the thermal expansion curve becomes small, close to zero, although it is not a clearly convex shape. The inflection point can be obtained by drawing a tangent to the thermal expansion curve in the temperature range before and after the change in the slope of the thermal expansion curve and calculating the temperature of the intersection. The temperature of this inflection point is defined as the "shoulder peak" temperature.

[0091] When a peak is obtained in the thermal expansion curve, the temperature of the peak is taken as the transition point. However, when a peak is not obtained in the thermal expansion curve but a "shoulder peak" is obtained, or when a "shoulder peak" is observed at a temperature lower than the temperature at which the peak is obtained, the temperature of the "shoulder peak" is taken as the transition point. The transition point that appears at the lowest temperature after the start of measurement is defined as the transition point of the anchor coat layer. Details of the measurement conditions are described in the Examples section.

[0092] The thickness of the anchor coat layer is preferably 0.01 μm or more, more preferably 0.05 μm or more, even more preferably 0.1 μm or more, and is preferably 10 μm or less, more preferably 5 μm or less, even more preferably 3 μm or less. If the thickness is the lower limit or more, for example, sufficient adhesion strength between the heat seal layer and the inorganic vapor deposition film can be obtained. If the thickness is the upper limit or less, for example, the anchor coat layer can be well formed on the heat seal layer.

[0093] <Inorganic vapor deposition film> The transfer film of the present disclosure includes an inorganic vapor deposition film. The inorganic vapor deposition film is preferably a layer formed by vapor deposition directly on one side of the heat seal layer, or on one side of the anchor coat layer when an anchor coat layer is provided.

[0094] The inorganic vapor deposition film is a layer that suppresses the permeation of gases such as oxygen gas and water vapor. Therefore, for example, a gas barrier laminate obtained by transferring a transfer layer from the transfer film of the present disclosure to a transferee has excellent gas barrier properties. When the inorganic vapor deposition film is an opaque layer, the inorganic vapor deposition film has a light-shielding property against sunlight and the like, and can also have an aroma-retaining property for the contents.

[0095] The inorganic vapor deposition film may be a metal vapor deposition film made of a metal, or may be a vapor deposition film made of an inorganic compound.

[0096] Examples of metals constituting the metal vapor deposition film include aluminum, chromium, tin, nickel, copper, silver, gold, and platinum. Among these, aluminum is preferred. That is, an aluminum vapor deposition film is preferred.

[0097] Examples of inorganic compounds constituting the above-mentioned deposited film include metal oxides, metal nitrides, metal carbides, indium tin oxide (ITO), and SiO X C Y Among these, metal oxides are preferred.

[0098] Examples of metal elements constituting the inorganic compound include aluminum (Al), silicon (Si), magnesium (Mg), calcium (Ca), potassium (K), tin (Sn), sodium (Na), boron (B), titanium (Ti), lead (Pb), zirconium (Zr), yttrium (Y), zinc (Zn), vanadium (V), barium (Ba), and chromium (Cr).

[0099] The average composition of the inorganic compound is, for example, AlO x , SiO x , SiOx C y As in, MO x Or MO x C y In the formula, M represents the above-mentioned metal element, and the values ​​of x and y each fall within a different range depending on the metal element.

[0100] For metal oxides, x can range from 0 to 1.5 for aluminum, 0 to 2 for silicon, 0 to 1 for magnesium, 0 to 1 for calcium, 0 to 0.5 for potassium, 0 to 2 for tin, 0 to 0.5 for sodium, 0 to 1.5 for boron, 0 to 1.5 for titanium, 0 to 2 for lead, 0 to 1 for zirconium, and 0 to 1.5 for yttrium.

[0101] MO x In the above, the upper limit of the range of x is the value when completely oxidized. For aluminum oxide, x is preferably in the range of 0.5 to 1.5, and for silicon oxide, x is preferably in the range of 1.0 to 2.0.

[0102] Among the metal oxides, aluminum oxide, silicon oxide, magnesium oxide, calcium oxide, boron oxide, titanium oxide, zirconium oxide and barium oxide are preferred, and aluminum oxide and silicon oxide are more preferred.

[0103] The inorganic vapor deposition film may be formed of one type of metal or inorganic compound, or may be formed of a combination of two or more types of metals or inorganic compounds. The inorganic vapor deposition film may be composed of one layer, or may be composed of two or more layers of the same or different compositions.

[0104] In the case of a multi-layer inorganic vapor deposition film, each layer can be vapor deposited so as to have high gas barrier properties, and therefore it is possible to obtain gas barrier properties even higher than those of a single layer. In the case of a multi-layer inorganic vapor deposition film, if each layer has a different composition, the inorganic vapor deposition film is a discontinuous layer with different compositions, and therefore it is possible to more efficiently suppress the permeation of oxygen gas, water vapor, and the like.

[0105] The thickness of the inorganic vapor deposition film is preferably 3 nm or more, more preferably 4 nm or more, and even more preferably 5 nm or more, and is preferably 300 nm or less, more preferably 250 nm or less, even more preferably 200 nm or less, and particularly preferably 80 nm or less or 60 nm or less. If the thickness is the lower limit or more, for example, sufficient oxygen barrier property and water vapor barrier property can be obtained. If the thickness is the upper limit or less, for example, the occurrence of cracks in the inorganic vapor deposition film can be suppressed.

[0106] In one embodiment, the thickness of the inorganic vapor deposition film made of aluminum oxide is preferably 3 nm or more, more preferably 5 nm or more, and preferably 100 nm or less, more preferably 50 nm or less. In one embodiment, the thickness of the inorganic vapor deposition film made of silicon oxide is preferably 3 nm or more, more preferably 10 nm or more, and preferably 300 nm or less, more preferably 50 nm or less. The thickness of the inorganic vapor deposition film made of silicon oxide is preferably 20 nm or more and 40 nm or less.

[0107] The inorganic vapor deposition film may be subjected to a surface treatment. This can improve the adhesion between the inorganic vapor deposition film and an adjacent layer (e.g., an adhesive layer). Examples of the surface treatment include physical surface treatments such as corona discharge treatment, ozone treatment, plasma treatment, glow discharge treatment, and sandblasting treatment; and chemical surface treatments such as oxidation treatment using chemicals.

[0108] <Protective layer> The transfer film of the present disclosure may further include a protective layer on the surface of the inorganic vapor deposition film opposite to the heat seal layer side, which can, for example, prevent the inorganic vapor deposition film from being scratched.

[0109] In one embodiment, the protective layer contains a resin component. Examples of the resin component include polyethylene, polypropylene, polystyrene, vinyl chloride resin, polyester, (meth)acrylic resin, urethane resin, melamine resin, and epoxy resin. The resin component is preferably, for example, urethane resin.

[0110] The content of the resin component in the protective layer may be 50% by mass or more, 75% by mass or more, 95% by mass or less, or 90% by mass or less.

[0111] The protective layer may contain an additive. Examples of the additive include a curing agent, an antistatic agent, an ultraviolet absorbing agent, a colorant, a heat stabilizer, and a silane coupling agent. Examples of the silane coupling agent include vinyl-based, epoxy-based, styryl-based, methacryl-based, acrylic-based, amino-based, isocyanurate-based, ureido-based, mercapto-based, sulfide-based, or isocyanate-based silane coupling agents.

[0112] The thickness of the protective layer is preferably 0.01 μm or more, more preferably 0.05 μm or more, and even more preferably 0.1 μm or more, and is preferably 5 μm or less, more preferably 3 μm or less, and even more preferably 1 μm or less.

[0113] For example, when the inorganic vapor deposition film is composed of a metal oxide such as aluminum oxide or silicon oxide, the transfer film of the present disclosure may have a barrier coat layer as a protective layer on the inorganic vapor deposition film, which can further improve the gas barrier properties of the barrier laminate, for example.

[0114] In one embodiment, the barrier coat layer contains a gas barrier resin, such as an ethylene-vinyl alcohol copolymer, polyvinyl alcohol, poly(meth)acrylonitrile, polyamides such as nylon 6, nylon 6,6, and polymetaxylylene adipamide (MXD6), polyesters, polyurethanes, and (meth)acrylic resins.

[0115] The content of the gas barrier resin in the barrier coat layer is preferably 50% by mass or more, more preferably 50% by mass or more, and even more preferably 75% by mass or more, and is preferably 95% by mass or less, more preferably 90% by mass or less. If the content is equal to or more than the lower limit, for example, the gas barrier property of the barrier laminate can be further improved.

[0116] The barrier coat layer can contain the above-mentioned additives.

[0117] The thickness of the barrier coat layer is preferably 0.01 μm or more, more preferably 0.1 μm or more, and preferably 10 μm or less, more preferably 5 μm or less. If the thickness is equal to or more than the lower limit, for example, the gas barrier properties of the barrier laminate can be improved. If the thickness is equal to or less than the upper limit, for example, the processability of the barrier laminate can be improved.

[0118] In another embodiment, the barrier coat layer is a gas barrier coating film formed by subjecting a composition containing a metal alkoxide and a water-soluble polymer to a polycondensation treatment by a sol-gel method in the presence of a sol-gel catalyst, water, an organic solvent, etc. By providing such a barrier coat layer on an inorganic vapor deposition film, the gas barrier property can be improved.

[0119] In one embodiment, the metal alkoxide is represented by the following general formula: R 1 n M(OR 2 ) m

[0120] In the formula, R 1 and R 2are each independently an organic group having 1 to 8 carbon atoms, M is a metal atom, n is an integer of 0 or more, m is an integer of 1 or more, and n+m represents the atomic valence of M.

[0121] R 1 and R 2 Examples of the organic group represented by the formula (1) include alkyl groups having 1 to 8 carbon atoms, specifically, methyl, ethyl, n-propyl, isopropyl, n-butyl, and isobutyl groups. Examples of the metal atom M include silicon, zirconium, titanium, and aluminum.

[0122] Examples of metal alkoxides that satisfy the above general formula include tetramethoxysilane (Si(OCH 3 ) 4 ), tetraethoxysilane (Si(OC 2 H 5 ) 4 ), tetrapropoxysilane (Si(OC 3 H 7 ) 4 ) and tetrabutoxysilane (Si(OC 4 H 9 ) 4 ) are mentioned.

[0123] It is preferable to use a silane coupling agent together with the metal alkoxide. As the silane coupling agent, a known organoalkoxysilane containing an organic reactive group can be used, and an organoalkoxysilane having an epoxy group is preferable. As the organoalkoxysilane having an epoxy group, for example, γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropylmethyldiethoxysilane, and β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane can be mentioned. It is preferable to use the silane coupling agent in an amount of 1 part by mass or more and 20 parts by mass or less with respect to 100 parts by mass of the metal alkoxide.

[0124] As the water-soluble polymer, polyvinyl alcohol and ethylene-vinyl alcohol copolymer are preferred. Either polyvinyl alcohol or ethylene-vinyl alcohol copolymer may be used, or both may be used in combination, depending on the desired physical properties such as oxygen barrier property, water vapor barrier property, water resistance, and weather resistance. Also, a gas barrier coating film obtained using polyvinyl alcohol and a gas barrier coating film obtained using an ethylene-vinyl alcohol copolymer may be laminated.

[0125] The content of the water-soluble polymer in the composition is preferably 5 parts by mass or more and 500 parts by mass or less relative to 100 parts by mass of the metal alkoxide. If the content is equal to or more than the lower limit, for example, the gas barrier property of the barrier laminate can be further improved. If the content is equal to or less than the upper limit, for example, the film formability of the composition can be further improved.

[0126] The sol-gel catalyst is preferably an acid or an amine compound. The amine compound is preferably a tertiary amine that is substantially insoluble in water and soluble in an organic solvent, such as N,N-dimethylbenzylamine, tripropylamine, tributylamine, and tripentylamine. Among these, N,N-dimethylbenzylamine is preferred.

[0127] The amount of the amine compound used is preferably 0.01 parts by mass or more, more preferably 0.03 parts by mass or more, and preferably 1.0 parts by mass or less, more preferably 0.3 parts by mass or less, based on 100 parts by mass of the metal alkoxide. If the amount used is the lower limit or more, for example, the catalytic effect can be improved. If the amount used is the upper limit or less, for example, the thickness of the gas barrier coating film can be made uniform.

[0128] The acid is suitably used as a catalyst for the sol-gel process, mainly as a catalyst for hydrolysis of metal alkoxides and silane coupling agents, etc. Examples of the acid include mineral acids such as sulfuric acid, hydrochloric acid, and nitric acid, and organic acids such as acetic acid and tartaric acid.

[0129] The amount of the acid used is preferably 0.001 mol or more and 0.05 mol or less per mol of the total amount of the metal alkoxide and the alkoxide portion (e.g., silicate portion) of the silane coupling agent. If the amount of the acid used is equal to or more than the lower limit, for example, the catalytic effect can be improved. If the amount of the acid used is equal to or less than the upper limit, for example, the thickness of the gas barrier coating film can be made uniform.

[0130] The composition preferably contains water in an amount of 0.1 mole or more, more preferably 0.8 mole or more, preferably 100 moles or less, more preferably 2 moles or less, per mole of the total amount of alkoxide. If the water content is equal to or more than the lower limit, for example, the gas barrier property of the barrier laminate can be further improved. If the water content is equal to or less than the upper limit, for example, the hydrolysis reaction can be carried out quickly.

[0131] The composition may contain an organic solvent, such as alcohol solvents such as methyl alcohol, ethyl alcohol, n-propyl alcohol, isopropyl alcohol, and n-butanol.

[0132] The thickness of the gas barrier coating film is preferably 0.01 μm or more, more preferably 0.1 μm or more, and preferably 100 μm or less, more preferably 50 μm or less. This can further improve the gas barrier properties of the barrier laminate. If the thickness is equal to or greater than the lower limit, for example, the gas barrier properties of the barrier laminate can be further improved, and the occurrence of cracks in the inorganic vapor deposition film can be suppressed. If the thickness is equal to or less than the upper limit, for example, the barrier laminate can be suitably used for the production of mono-material packaging containers.

[0133] <Adhesive layer> The transfer film of the present disclosure may have an adhesive layer on the surface opposite to the heat seal layer side of the inorganic vapor deposition film. In the transfer method described below, the adhesive layer is a layer for bonding a transfer recipient (e.g., a paper member having a paper substrate) to a support substrate, a heat seal layer, and a transfer film having an inorganic vapor deposition film. The transfer film does not need to have an adhesive layer, and for example, an adhesive layer may be provided on the transfer recipient.

[0134] In one embodiment, the adhesive layer is a layer that contacts the inorganic vapor deposition film. In this embodiment, the adhesive layer protects the inorganic vapor deposition film. For example, when a bending load is applied to the transfer film, the adhesive layer suppresses the occurrence of cracks in the inorganic vapor deposition film, and suppresses the deterioration of the gas barrier property even when microcracks begin to occur in the inorganic vapor deposition film after the bending load. The details of the adhesive layer will be described later, and a detailed explanation thereof will be omitted in this section.

[0135] <Layer structure of transfer film> Several examples of the layer structure of the transfer film of the present disclosure are given below. ·Inorganic vapor deposition film / HS layer / supporting base material ·Inorganic vapor deposited film / AC layer / HS layer / support base material ·Protective layer / inorganic vapor deposition film / HS layer / supporting substrate ·Protective layer / Inorganic vapor deposition film / AC layer / HS layer / Support base material ·Protective layer / Protective layer / Inorganic vapor deposition film / HS layer / Support substrate ·Protective layer / protective layer / inorganic vapor deposition film / AC layer / HS layer / supporting substrate

[0136] "HS layer" means heat seal layer, "AC layer" means anchor coat layer, and " / " means interlayer.

[0137] [Transfer film manufacturing method] The method for producing the transfer film of the present disclosure may include a step of forming a heat seal layer on a supporting substrate (hereinafter also referred to as a "heat seal layer forming step"), a step of forming an anchor coat layer on the heat seal layer as necessary (hereinafter also referred to as an "anchor coat layer forming step"), and a step of forming an inorganic vapor deposition film on the heat seal layer or the anchor coat layer (hereinafter also referred to as a "vapor deposition film forming step"). The above-mentioned production method may include a step of forming a protective layer on the inorganic vapor deposition film (hereinafter also referred to as a "protective layer forming step").

[0138] <Heat seal layer forming process> The heat seal layer can be formed, for example, by applying a coating liquid for the heat seal layer to one side of the support substrate and drying it. The heat seal layer is preferably provided on the side of the support substrate that has not been subjected to an easy-adhesion treatment or on the side on which an easy-adhesion layer is not formed.

[0139] The coating liquid for the heat-seal layer is preferably a coating liquid capable of forming a coating film on a supporting substrate and capable of forming a coating film having excellent peelability from the supporting substrate and heat-sealability. The details of the coating liquid for the heat-seal layer are as described above.

[0140] In one embodiment, the coating liquid for the heat seal layer is applied onto the supporting substrate and dried. Examples of the method for applying the coating liquid for the heat seal layer include known coating methods such as gravure coating, reverse coating, air knife coating, comma coating, die coating, blade coating, roll coating, bar coating, curtain coating, spray coating, lip coating, and dipping.

[0141] The applied coating liquid for the heat seal layer can be dried, for example, by hot air drying, hot roll drying, infrared radiation, or other heat application methods. The drying temperature is preferably 50° C. or higher and 150° C. or lower.

[0142] <Anchor coat layer forming process> By providing an anchor coat layer on the heat seal layer, the adhesion of the inorganic vapor deposition film can be improved and the vapor deposition surface can be smoothed. The anchor coat layer may not be provided depending on the required level of gas barrier property and the required interlayer strength.

[0143] The anchor coating agent can be prepared, for example, by mixing the above-mentioned resin component or its precursor resin (e.g., thermosetting resin), and optionally a curing agent, optionally an additive, and a solvent. Details of these components are as described above, and examples of the solvent include the same solvent as that of the coating liquid for the heat seal layer.

[0144] The anchor coat layer can be formed, for example, by applying an anchor coat agent onto the heat seal layer and drying it. The method for applying the anchor coat agent includes the above-mentioned known application methods. The method for drying the applied anchor coat agent includes, for example, hot air drying, hot roll drying, and a method of applying heat such as infrared irradiation. The drying temperature is preferably 50°C or higher and 150°C or lower.

[0145] <Deposited film formation process> The inorganic vapor deposition film is preferably a layer formed by vapor deposition directly on one side of the heat seal layer or the anchor coat layer. Examples of the method for forming the inorganic vapor deposition film include physical vapor deposition (PVD) methods such as vacuum deposition, sputtering, ion plating, and cluster ion beam; and chemical vapor deposition (CVD) methods such as plasma chemical vapor deposition, thermal chemical vapor deposition, and photochemical vapor deposition. The inorganic vapor deposition film may be a composite film having two or more different layers formed by using both physical vapor deposition and chemical vapor deposition. Examples of the heating means include resistance heating means, induction heating means, and electron beam heating means.

[0146] The gas pressure in the deposition chamber was 10 -8 mbar or more than 10 -2In the case of forming an inorganic vapor deposition film made of an inorganic compound, for example, oxygen gas, nitrogen gas, or carbon dioxide gas is introduced as a reactive gas. In the case of forming an inorganic vapor deposition film made of a metal oxide, the gas pressure is preferably 10 mbar or less after the introduction of oxygen gas. -6 mbar or more than 10 -1 mbar or less is preferred.

[0147] The amount of the reactive gas introduced varies depending on the size of the deposition machine, etc. For the reactive gas such as oxygen gas to be introduced, an inert gas such as argon gas, helium gas, or nitrogen gas may be used as a carrier gas to the extent that no problems occur.

[0148] When a roll-shaped transfer substrate is used and an inorganic vapor deposition film is formed continuously, the conveying speed of the transfer substrate on which a heat seal layer and, if necessary, an anchor coat layer are formed is, for example, 10 m / min or more and 800 m / min or less.

[0149] When forming an inorganic deposition film, Ar gas, O 2 Or N 2 By pretreating the surface of the layer on which the inorganic vapor deposition film is to be formed by vapor deposition using a pretreatment agent such as a fluorine-based solvent, the surface of the layer on which the inorganic vapor deposition film is to be formed can be cleaned and polar groups or free radicals or the like can be generated on the surface of the layer, thereby increasing the adhesion between the inorganic vapor deposition film and the layer.

[0150] In one embodiment, the PVD method uses, for example, a winding-type vapor deposition machine, and a substrate unwound from a winding roll is placed in a vapor deposition chamber, where a vapor deposition source heated in a crucible is evaporated, and an inorganic vapor deposition film is formed on the substrate on a cooled coating drum while, if necessary, oxygen gas or the like is ejected from an oxygen gas outlet, and then the substrate is wound up on a take-up roll.

[0151] In one embodiment, in the PE-CVD method, for example, a mixed gas containing an organosilicon compound as a monomer gas, oxygen gas, an inert gas, etc. is introduced into a deposition chamber, and plasma is generated to form an inorganic deposition film composed of silicon oxide or the like on a substrate.

[0152] The substrate includes a transfer base material, a heat seal layer, and an optional anchor coat layer. In this manner, a transfer film is obtained that includes a transfer base material, a heat seal layer, and an optional anchor coat layer, and an inorganic vapor deposition film in this order in the thickness direction.

[0153] <Protective layer formation process> The protective layer can be formed, for example, by applying a protective layer coating liquid onto an inorganic vapor deposition film and drying it. The method for applying the protective layer coating liquid includes the above-mentioned known coating methods. The method for drying the applied protective layer coating liquid includes, for example, hot air drying, hot roll drying, and a method of applying heat such as infrared irradiation. The drying temperature is preferably 50°C or higher and 150°C or lower.

[0154] The coating liquid for the protective layer can be prepared, for example, by mixing the above-mentioned resin components, a curing agent if necessary, an additive if necessary, and a solvent. The details of these components are as described above, and the solvent may be the same as that of the coating liquid for the heat seal layer.

[0155] The barrier coat layer as a protective layer can be formed, for example, by dissolving or dispersing a material such as a gas barrier resin in water or an appropriate organic solvent, and applying the resulting coating liquid onto the inorganic vapor deposition film and drying it. The barrier coat layer can also be formed, for example, by applying and drying a commercially available barrier coating agent.

[0156] In one embodiment, the barrier coat layer is the gas barrier coating film described above. The gas barrier coating film can be formed, for example, by applying the composition containing a metal alkoxide and a water-soluble polymer by a conventionally known coating method, and subjecting the composition to a polycondensation treatment by a sol-gel method.

[0157] Hereinafter, one embodiment of the method for forming a gas barrier coating film will be described. First, a composition is prepared by mixing a metal alkoxide, a water-soluble polymer, a sol-gel catalyst, water, an organic solvent, and, if necessary, a silane coupling agent, etc. In the composition, a polycondensation reaction gradually proceeds.

[0158] Next, the composition is applied onto the inorganic vapor deposition film by a conventionally known coating method and dried. This drying process further advances the polycondensation reaction of the metal alkoxide and the water-soluble polymer (and the silane coupling agent, if the composition contains a silane coupling agent) to form a composite polymer layer.

[0159] Finally, the composition is heated at a temperature of preferably 20° C. to 250° C., more preferably 50° C. to 220° C., for preferably 1 second to 10 minutes, thereby forming a gas barrier coating film.

[0160] [Barrier laminate] In one embodiment, the barrier laminate of the present disclosure includes a substrate such as a paper substrate, an adhesive layer, an inorganic vapor deposition film, and a heat seal layer in this order in the thickness direction. In one embodiment, the barrier laminate of the present disclosure further includes an anchor coat layer between the inorganic vapor deposition film and the heat seal layer. Here, the inorganic vapor deposition film is in contact with the heat seal layer or the anchor coat layer (if an anchor coat layer is provided).

[0161] In one embodiment, the barrier laminate of the present disclosure includes a substrate such as a paper substrate, an adhesive layer, an inorganic vapor deposition film, and a heat seal layer in this order in the thickness direction. In one embodiment, the barrier laminate of the present disclosure further includes an anchor coat layer between the inorganic vapor deposition film and the heat seal layer. The barrier laminate of this embodiment does not include a release layer between the inorganic vapor deposition film and the heat seal layer.

[0162] One embodiment of the barrier laminate of the present disclosure is shown in Fig. 3. The barrier laminate 1 of Fig. 3 includes a substrate 10, an adhesive layer 20, an inorganic vapor deposition film 30, and a heat seal layer 40 in this order in the thickness direction.

[0163] Another embodiment of the barrier laminate of the present disclosure is shown in Fig. 4. The barrier laminate 1 in Fig. 4 includes a printed layer 12, a substrate 10, an adhesive layer 20, an inorganic vapor deposition film 30, an anchor coat layer 32, and a heat seal layer 40, in this order in the thickness direction.

[0164] Since the barrier laminate of the present disclosure does not have a release layer between the heat seal layer and the inorganic vapor deposition film, the adhesive strength between these layers is high, and therefore the barrier laminate of the present disclosure is prevented from causing delamination during its production process and use.

[0165] The release layer is a layer that is usually provided as a surface layer on the transfer support side of the transfer layer in a conventional transfer film that includes a transfer support and a transfer layer in order to improve the releasability of the transfer layer from the transfer support. That is, the transfer layer includes a release layer as a surface layer on the transfer support side.

[0166] The release layer is usually a layer containing a release agent. Examples of the release agent include waxes such as silicone wax, silicone oil, silicone resin, fluororesin, and phosphoric acid ester. In one embodiment, the release layer contains a resin component. Examples of the resin component include polyolefin, vinyl resin, styrene resin, (meth)acrylic resin, polyester, polyurethane, polycarbonate, polyamide, polyimide, and cellulose resin.

[0167] <Base material> The barrier laminate of the present disclosure includes a substrate.

[0168] Examples of the substrate include a paper substrate and the resin film described above as the supporting substrate. Among these, a paper substrate is preferred. A barrier laminate having a paper substrate as the substrate is also called "barrier paper".

[0169] Examples of the paper substrate include paper materials such as kraft paper, pure white roll paper, fine paper, medium quality paper, glassine paper, Kent paper, processed base paper, paperboard, and synthetic paper. Examples of the paper substrate include paper substrates having a sealing layer or resin layer formed on one or both sides of the paper material, such as clay-coated paper, lightly coated printing paper, coated printing paper (e.g., coated paper, cast-coated paper, and art paper), resin-coated paper, release base paper, and double-sided coated release base paper.

[0170] The paper base material may contain additives. Examples of additives include sizing agents, lubricants, antioxidants, UV absorbers, light stabilizers, antistatic agents, fluorescent brighteners, fluorescent decolorizers, fillers, reinforcing agents, pigments, and dyes. The additives can be added in any amount depending on the purpose as long as they do not adversely affect other performances.

[0171] The surface of the substrate on the side of the adhesive layer may be previously subjected to a physical surface treatment such as corona discharge treatment, ozone treatment, plasma treatment, glow discharge treatment, sandblasting treatment, etc., or a chemical surface treatment such as oxidation treatment using chemicals.

[0172] In one embodiment, the paper substrate comprises the above-mentioned paper material and a filler layer or a resin layer formed on the adhesive layer side of the paper material. The filler layer has a function of suppressing the adhesive constituting the adhesive layer from penetrating into the paper material and stabilizing the adhesive strength of the adhesive layer.

[0173] In one embodiment, the filling layer or the resin layer contains a resin component. Examples of the resin component include polyolefins such as polyethylene and polypropylene, vinyl resins such as vinyl chloride resins and vinyl acetate resins, styrene resins such as styrene-butadiene copolymers, (meth)acrylic resins, polyesters, polyamides, polyurethanes, and cellulose resins; and thermoplastic resins such as cured products of thermosetting resins.

[0174] In one embodiment, the filler layer or the resin layer contains an additive. Examples of the additive include a lubricant, an antioxidant, an ultraviolet absorber, a light stabilizer, an antistatic agent, a fluorescent brightener, a fluorescent decolorizing agent, a filler, a reinforcing agent, a pigment, and a dye. The filler layer or the resin layer preferably contains a filler. Examples of the filler include clay, silica, calcium carbonate, titanium oxide, and zinc oxide.

[0175] The filling layer or resin layer can be formed by, for example, a coating method or an extrusion coating method. The thickness of the filling layer or resin layer is, for example, 0.1 μm or more and 30 μm or less.

[0176] Generally, the surface of paper is porous and uneven, so when forming an inorganic vapor deposition film directly on the paper, it may be preferable to form a filler layer having a thickness of 20 μm or more on the paper surface. However, in the present disclosure, since barrier paper can be manufactured by the transfer method described below, it is not necessary to directly form an inorganic vapor deposition film on the paper. Therefore, it is not necessary to form such a thick filler coat layer on the paper surface.

[0177] Furthermore, in general, when a paper material is placed in a vapor deposition device and an inorganic vapor deposition film is formed under reduced pressure, paper dust generated from the paper material can prevent the pressure inside the vapor deposition device from being reduced to a pressure suitable for vapor deposition. In such cases, it is difficult to form a stable inorganic vapor deposition film, and the adhesion between the formed inorganic vapor deposition film and the paper material is likely to become insufficient, which can lead to unstable gas barrier properties. However, in the present disclosure, since barrier paper can be manufactured by the transfer method described below, there is no need to place the paper material in a vapor deposition device and directly form an inorganic vapor deposition film on the paper material. Therefore, the above-mentioned problems can be avoided.

[0178] In this manner, in the present disclosure, the paper substrate can be a substrate made of paper and not impregnated with a resin component, a clay material, etc. Also, in the present disclosure, the paper substrate can be a substrate made of paper and not provided with any of a filling layer, a resin layer, and a clay coat layer.

[0179] The substrate such as a paper substrate may be composed of one layer, or may be composed of two or more layers of the same or different substrates. The substrates can be laminated by any lamination means via a conventionally known adhesive layer.

[0180] The thickness of the base material such as a paper base material is preferably 10 μm or more, more preferably 30 μm or more, and even more preferably 40 μm or more, and is preferably 1,500 μm or less, more preferably 500 μm or less, and even more preferably 300 μm or less. The basis weight of the paper base material is preferably 30 g / m 2 More preferably, 50 g / m 2 More preferably, it is 600 g / m 2 Less than 450g / m 2 When the substrate is constructed with multiple layers, the thickness of the substrate means the total thickness of the multiple layers of the substrate. The same applies to the basis weight.

[0181] Such thickness and / or basis weight can provide, for example, appropriate strength and rigidity to the barrier laminate. If the thickness and / or basis weight is equal to or greater than the lower limit, for example, the occurrence of curling and waviness during the production of the barrier laminate can be suppressed. If the thickness and / or basis weight is equal to or less than the upper limit, the strength and rigidity fall within an appropriate range, and a decrease in work efficiency can be suppressed.

[0182] <Print layer> In one embodiment, the barrier laminate of the present disclosure comprises a printed layer on a substrate such as a paper substrate. The barrier laminate of the present disclosure may comprise a printed layer on the surface of the substrate opposite to the adhesive layer side and / or on the surface of the substrate opposite to the adhesive layer side, and preferably comprises a printed layer on the surface of the substrate opposite to the adhesive layer side.

[0183] The printing layer includes, for example, an image. Examples of the image include characters, figures, symbols, pictures, patterns, and combinations thereof. The printing layer is provided, for example, for displaying the contents of the packaging material, displaying the expiration date, displaying the manufacturer and seller, decoration, and imparting an aesthetic feel.

[0184] In one embodiment, the print layer is formed using a print layer composition such as a thermoplastic resin composition, a thermosetting resin composition, or an energy ray curable resin composition, each of which contains a colorant. Specifically, the print layer contains a thermoplastic resin, a cured product of a thermosetting resin, or a cured product of an energy ray curable resin, and a colorant.

[0185] The thermoplastic resin composition contains a thermoplastic resin and a colorant. Examples of the thermoplastic resin include polyolefin, vinyl resin, styrene-based resin, (meth)acrylic resin, polyester, polyurethane, polycarbonate, polyamide, polyimide, cellulose-based resin, petroleum resin, and fluororesin.

[0186] The thermoplastic resin composition may contain additives, such as lubricants, antioxidants, ultraviolet absorbers, light stabilizers, antistatic agents, fluorescent brighteners, fluorescent decolorizing agents, fillers, reinforcing agents, pigments, and dyes.

[0187] The thermosetting resin composition is a composition that contains a thermosetting resin, a colorant, and optionally a curing agent, and is cured by heating. In one embodiment, the thermosetting resin composition is a so-called thermosetting ink.

[0188] Examples of the thermosetting resin include phenol resin, melamine resin, urea resin, epoxy resin, unsaturated polyester, thermosetting polyurethane, silicone resin, and (meth)acrylic thermosetting resin. Examples of the curing agent include epoxy curing agents and isocyanate curing agents. The thermosetting resin composition may contain the above-mentioned additives.

[0189] The energy ray curable resin composition is a composition that contains a compound having an energy ray curable functional group (hereinafter also referred to as "energy ray curable compound") and a colorant, and is cured by irradiation with energy rays. In one embodiment, the energy ray curable resin composition is a so-called ultraviolet ray curable ink, and is preferably a (meth)acrylic ultraviolet ray curable ink.

[0190] Examples of the energy beam include electromagnetic waves such as ultraviolet rays, infrared rays, X-rays, and gamma rays; and charged particle beams such as electron beams, proton beams, and neutron beams. Among these, ultraviolet rays are preferred from the viewpoints of curing speed, availability of an irradiation source, and cost.

[0191] Examples of the energy ray curable functional group include ethylenically unsaturated groups such as (meth)acryloyl group, vinyl group, and allyl group; and epoxy group and oxetanyl group. Examples of the energy ray curable compound include a compound having an ethylenically unsaturated group, preferably a compound having two or more ethylenically unsaturated groups, and more preferably a polyfunctional (meth)acrylate compound. As the polyfunctional (meth)acrylate compound, both monomers and oligomers can be used.

[0192] When the energy ray-curable compound is an ultraviolet ray-curable compound, the energy ray-curable composition (ultraviolet ray-curable resin composition) preferably contains at least one selected from a photopolymerization initiator and a photopolymerization accelerator. The energy ray-curable resin composition may contain the above-mentioned additives.

[0193] Examples of the colorant include pigments and dyes. Specific examples of the pigment include titanium oxide, zinc oxide, carbon black, iron oxide, yellow iron, ultramarine, metallic pigments, pearl pigments, and fluorescent pigments. The printing layer may be a high-brightness layer having a high metallic luster.

[0194] The printing layer composition may contain an organic solvent and / or water from the viewpoint of improving the coating properties, etc. Examples of the organic solvent include hydrocarbon solvents such as toluene and xylene, ketone solvents such as acetone and methyl ethyl ketone, ester solvents such as ethyl acetate, cellosolve acetate, and butyl cellosolve acetate, and alcohol solvents such as propanol.

[0195] For example, the printing layer composition can be applied to a substrate such as a paper substrate and dried, followed by heating at a temperature required for curing in the case of a thermosetting resin composition, or irradiating with energy rays in the case of an energy ray-curable resin composition, to form a printing layer. If the printing layer composition does not contain an organic solvent and / or water, drying is not necessary.

[0196] Examples of methods for forming the printed layer include letterpress printing, flexographic printing, gravure printing, offset printing, screen printing, inkjet printing, and thermal transfer printing. The printed layer may be provided on the entire surface of the substrate, or may be provided on only a part of the substrate.

[0197] In one embodiment, the printing layer includes a sublimation dye. The printing layer of this embodiment can be formed, for example, by sublimation transfer printing using a thermal transfer sheet.

[0198] The thickness of the printed layer is preferably 0.01 μm or more, more preferably 0.5 μm or more, even more preferably 1 μm or more, and is preferably 30 μm or less, more preferably 10 μm or less, even more preferably 5 μm or less.

[0199] <Adhesive layer> The barrier laminate of the present disclosure includes an adhesive layer between the substrate and the inorganic vapor deposition film. In a transfer method described below, the adhesive layer is a layer for bonding a transfer-receiving body such as a paper member having a paper substrate to a transfer film having a supporting substrate, a heat seal layer, and an inorganic vapor deposition film.

[0200] In one embodiment, the adhesive layer is a layer that comes into contact with the inorganic vapor deposition film. In this embodiment, the adhesive layer protects the inorganic vapor deposition film. For example, when a bending load is applied to the barrier laminate, the adhesive layer suppresses the occurrence of cracks in the inorganic vapor deposition film, and suppresses the deterioration of the gas barrier properties even when microcracks start to occur in the inorganic vapor deposition film after the bending load.

[0201] The thickness of the adhesive layer is preferably 0.5 μm or more, more preferably 1 μm or more, and is preferably 20 μm or less, more preferably 10 μm or less. The basis weight of the adhesive layer is preferably 1 g / m 2 More preferably, 2 g / m 2 More preferably, it is 20 g / m 2 Less than 10 g / m 2 The following is the result.

[0202] The adhesive layer can be formed using a conventionally known adhesive. The adhesive may be any one-component curing type, two-component curing type, or non-curing type adhesive. The adhesive may be a solventless adhesive or a solvent-based adhesive. The adhesive layer may be formed, for example, by a non-solvent lamination method using a non-solvent adhesive, or by a dry lamination method using a dry lamination adhesive. An anchor coat layer may be formed first on the layer on which the adhesive layer is to be formed, and then the adhesive layer may be formed.

[0203] The anchor coat layer can be formed using, for example, an anchor coat agent such as an isocyanate-based (urethane-based), polyethyleneimine-based, polybutadiene-based, or organic titanium-based; or an anchor coat agent such as a (meth)acrylic resin-based, polyurethane-based, polyester-based, epoxy-based, polyvinyl acetate-based, polyvinyl chloride-based, or cellulose resin-based.

[0204] Examples of adhesives include two-component curing urethane adhesives, polyester polyurethane adhesives, polyether polyurethane adhesives, (meth)acrylic adhesives, polyester adhesives, polyether adhesives, polyamide adhesives, epoxy adhesives, rubber adhesives, polyolefin adhesives, acid-modified polyolefin adhesives, polyvinyl acetate adhesives, and polyvinyl chloride adhesives. Acid-modified polyolefin resins are resins obtained by acid-modifying polyolefin resins by graft polymerization or copolymerization using unsaturated carboxylic acids or their anhydrides, such as (meth)acrylic acid, maleic acid, maleic anhydride, fumaric acid, and itaconic acid.

[0205] A urethane-based resin composition is preferred as an adhesive for forming an adhesive layer between a transfer object such as a paper substrate and an inorganic vapor deposition film. This allows, for example, a gas barrier adhesive layer to be formed. That is, the adhesive layer is preferably a layer formed using a urethane-based resin composition. The urethane-based resin composition preferably contains a polyol having two or more hydroxyl groups in one molecule and an isocyanate compound having two or more isocyanate groups in one molecule. The urethane-based resin composition may further contain a phosphoric acid compound or an inorganic compound. The urethane resin composition may be of a solventless type or a solvent type.

[0206] Commercially available adhesives include, for example, dry laminating adhesives (main agent RU-40 / hardener H-1, and main agent RU-77T / hardener H-7) manufactured by Rock Paint Co., Ltd.

[0207] The adhesive layer and the urethane resin composition may contain additives, such as antioxidants, ultraviolet absorbers, light stabilizers, antistatic agents, fluorescent brighteners, fluorescent decolorizing agents, fillers, reinforcing agents, antiblocking agents, flame retardants, crosslinking agents, pigments, and dyes.

[0208] In one embodiment, the adhesive layer has a glass transition temperature (Tg) in the range of preferably -30°C or higher, more preferably 0°C or higher, and even more preferably 25°C or higher, and preferably 80°C or lower, more preferably 70°C or lower, and even more preferably 70°C or lower. If Tg is equal to or lower than the upper limit, the adhesive layer tends to have excellent flexibility around room temperature and excellent adhesion to layers adjacent to the adhesive layer. If Tg is equal to or higher than the lower limit, the adhesive layer tends to have excellent cohesive strength, and therefore excellent adhesion.

[0209] The adhesive layer can be formed, for example, by applying an adhesive onto the substrate and / or inorganic vapor deposition film and optionally drying it by a method such as direct gravure roll coating, gravure roll coating, kiss coating, reverse roll coating, Fontaine method, and transfer roll coating.

[0210] <Polyol with two or more hydroxyl groups in one molecule> The polyol having two or more hydroxyl groups in one molecule may be, for example, a polyol having two or more hydroxyl groups in one molecule and at least one selected from a polyester structural part, a polyester polyurethane structural part, a polyether structural part, and a polyether polyurethane structural part as a main skeleton, and is preferably a polyol having two or more hydroxyl groups in one molecule and at least one selected from a polyester structural part and a polyester polyurethane structural part as a main skeleton, and more preferably a polyol having two or more hydroxyl groups in one molecule and a polyester structural part as a main skeleton. The polyester structural part can be obtained, for example, by polycondensation reaction of a polyvalent carboxylic acid and a polyvalent hydroxy compound.

[0211] The polycarboxylic acids refer to polycarboxylic acids, anhydrides thereof, and ester-forming derivatives thereof. Examples of the polycarboxylic acids include aliphatic polycarboxylic acids and aromatic polycarboxylic acids.

[0212] Examples of the aliphatic polycarboxylic acid include succinic acid, glutaric acid, adipic acid, azelaic acid, sebacic acid, dodecanedicarboxylic acid, and 1,4-cyclohexanedicarboxylic acid.

[0213] Examples of aromatic polycarboxylic acids include o-phthalic acid, isophthalic acid, terephthalic acid, 1,2-naphthalenedicarboxylic acid, 1,8-naphthalenedicarboxylic acid, 2,3-naphthalenedicarboxylic acid, 1,4-naphthalenedicarboxylic acid, 2,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, naphthalic acid, biphenyldicarboxylic acid, and 1,2-bis(phenoxy)ethane-p,p'-dicarboxylic acid; and trivalent or higher carboxylic acids such as trimellitic acid and pyromellitic acid. Among these, o-aromatic dicarboxylic acids are preferred. Examples of o-aromatic dicarboxylic acids include o-phthalic acid, 1,2-naphthalenedicarboxylic acid, 1,8-naphthalenedicarboxylic acid, and 2,3-naphthalenedicarboxylic acid.

[0214] Examples of polyhydric hydroxy compounds include aliphatic polyhydric alcohols such as aliphatic diols such as ethylene glycol, propylene glycol, butylene glycol, neopentyl glycol, cyclohexanedimethanol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, methylpentanediol, dimethylbutanediol, butylethylpropanediol, diethylene glycol, triethylene glycol, tetraethylene glycol, dipropylene glycol and tripropylene glycol; Aromatic polyhydric phenols such as hydroquinone, resorcinol, catechol, naphthalenediol, biphenol, bisphenol A, hisphenol F and tetramethylbiphenol, and their alkylene oxide adducts; and Hydrogenated alicyclic compounds of the above aromatic polyhydric phenols; Examples include:

[0215] The polyvalent carboxylic acid-derived structural part constituting the polyester structural part or the polyester polyurethane structural part preferably has a structural part derived from an o-aromatic dicarboxylic acid. It is preferable that 70% by mass or more and 100% by mass or less of the polyvalent carboxylic acid-derived structural parts constituting the polyester structural part or the polyester polyurethane structural part are structural parts derived from an o-aromatic dicarboxylic acid. The o-aromatic dicarboxylic acid refers to an o-aromatic dicarboxylic acid, an anhydride thereof, and an ester-forming derivative thereof.

[0216] <Isocyanate compound with two or more isocyanate groups in one molecule> The isocyanate compound having two or more isocyanate groups in one molecule may be either an aromatic compound or an aliphatic compound, and may be either a low molecular weight compound or a high molecular weight compound, so long as it has two or more isocyanate groups in one molecule. For example, a diisocyanate compound having two isocyanate groups and a polyisocyanate compound having three or more isocyanate groups may be mentioned. Also included are blocked isocyanate compounds obtained by addition reaction using a known isocyanate blocking agent by a known and commonly used appropriate method.

[0217] The isocyanate compound is preferably a compound having an aromatic ring in the main skeleton, and more preferably a compound having a polyurethane structure containing an aromatic ring in the main skeleton.

[0218] From the viewpoint of adhesiveness, polyisocyanate compounds are preferred, and from the viewpoint of gas barrier properties, polyisocyanate compounds having aromatic rings are more preferred. Isocyanate compounds containing a meta-xylene skeleton are more preferred because they are expected to improve gas barrier properties not only through hydrogen bonds of urethane groups but also through π-π stacking between aromatic rings.

[0219] Specific examples of the isocyanate compound include tetramethylene diisocyanate, hexamethylene diisocyanate, toluene diisocyanate, diphenylmethane diisocyanate, hydrogenated diphenylmethane diisocyanate, metaxylylene diisocyanate, hydrogenated xylylene diisocyanate, and isophorone diisocyanate. Also included are trimers of these isocyanate compounds. Also included are adducts, biuret compounds, or allophanates obtained by reacting an excess amount of these isocyanate compounds with an active hydrogen-containing low molecular weight compound or an active hydrogen-containing high molecular weight compound.

[0220] Examples of the active hydrogen-containing low molecular weight compound include ethylene glycol, propylene glycol, metaxylylene alcohol, 1,3-bishydroxyethylbenzene, 1,4-bishydroxyethylbenzene, trimethylolpropane, glycerol, pentaerythritol, erythritol, sorbitol, ethylenediamine, monoethanolamine, diethanolamine, triethanolamine, metaxylylenediamine, and alkylene oxide adducts thereof. Examples of the active hydrogen-containing polymer compound include polyester, polyether polyol, and polyamide.

[0221] <Inorganic vapor deposition film> The barrier laminate of the present disclosure includes an inorganic vapor deposition film. The inorganic vapor deposition film is preferably a layer formed by vapor deposition directly on one side of the heat seal layer, or on one side of the anchor coat layer when an anchor coat layer is provided. The details of the inorganic vapor deposition film are as described above, and will not be described here.

[0222] <Protective layer> The barrier laminate of the present disclosure may have a protective layer on the surface of the inorganic vapor deposition film opposite to the heat seal layer side. This can, for example, prevent the inorganic vapor deposition film from being scratched. Details of the protective layer are as described above, and will not be described here.

[0223] <Anchor coat layer> The barrier laminate of the present disclosure may further include an anchor coat layer between the heat seal layer and the inorganic vapor deposition film. By providing the anchor coat layer, the adhesion between the heat seal layer and the inorganic vapor deposition film can be increased, and the occurrence of peeling between these layers can be suppressed. For example, the anchor coat layer is in contact with the inorganic vapor deposition film on one side and in contact with the heat seal layer on the other side. Details of the anchor coat layer are as described above, and will not be described here.

[0224] <Heat seal layer> The barrier laminate of the present disclosure includes a heat seal layer as a surface layer on one side. In one embodiment, the heat seal layer functions as a heat seal layer. For example, when the barrier laminate is used as a packaging material, the heat seal layer functions as a heat sealable sealant layer. In addition, when the barrier laminate is manufactured by a transfer method described later, the heat seal layer also functions as a peeling layer from the supporting substrate. The details of the heat seal layer are as described above, and will not be described in this section.

[0225] <Functional layer> The barrier laminate of the present disclosure may include a functional layer in addition to the layers described above. The functional layer is a layer that imparts functions such as light blocking properties, mechanical strength, deformation resistance, impact resistance, pinhole resistance, heat resistance, sealability, quality maintenance, workability, and hygiene to the barrier laminate.

[0226] In one embodiment, the functional layer contains a resin component, such as polyolefin, vinyl resin, styrene-based resin, (meth)acrylic resin, polyester, polyurethane, polycarbonate, polyamide, polyimide, fluorine-based resin, cellulose-based resin, and ionomer resin.

[0227] The functional layer can contain the above-mentioned additives according to its function. The thickness of the functional layer is, for example, not less than 1 μm and not more than 300 μm.

[0228] <Layer structure and uses of barrier paper> Some examples of layer configurations of the barrier paper of the present disclosure are given below. ·Paper base material / adhesive layer / inorganic vapor deposition film / HS layer ·Paper base material / adhesive layer / inorganic vapor deposition film / AC layer / HS layer ·Paper base material / adhesive layer / protective layer / inorganic vapor deposition film / HS layer ·Paper base material / adhesive layer / protective layer / inorganic vapor deposition film / AC layer / HS layer Printing layer / paper base material / adhesive layer / inorganic vapor deposition film / HS layer Printing layer / paper base material / adhesive layer / inorganic vapor deposition film / AC layer / HS layer Printing layer / paper base material / adhesive layer / protective layer / inorganic vapor deposition film / HS layer Printing layer / paper base material / adhesive layer / protective layer / inorganic vapor deposition film / AC layer / HS layer ·Paper base material / adhesive layer / protective layer / protective layer / inorganic vapor deposition film / HS layer ·Paper base material / adhesive layer / protective layer / protective layer / inorganic vapor deposition film / AC layer / HS layer Printing layer / paper base material / adhesive layer / protective layer / protective layer / inorganic vapor deposition film / HS layer Printing layer / paper base material / adhesive layer / protective layer / protective layer / inorganic vapor deposition film / AC layer / HS layer

[0229] "HS layer" means heat seal layer, "AC layer" means anchor coat layer, and " / " means interlayer. The paper substrate may be a paper material / sealing layer (or resin layer). In this case, for example, the "paper substrate / adhesive layer" in the above layer structure becomes a "paper material / sealing layer (or resin layer) / adhesive layer". Instead of the paper substrate, a resin film may be used, or a substrate that is difficult to directly vapor-deposit (such as wood) may be used.

[0230] Compared to gas barrier plastic films, the barrier paper of the present disclosure has a paper base material, and therefore has a high paper content and a low plastic content, which can contribute to reducing plastic waste, makes it easier to recycle and biodegrade, does not damage incinerators, and reduces incineration residues.

[0231] The oxygen permeability of the barrier laminate of the present disclosure, such as the barrier paper, is 10 cc / m 2 / 24hr / atm or less is preferable, 5cc / m 2 / 24hr / atm or less is more preferable, 3cc / m 2 / 24hr / atm or less is more preferable, and 1.5cc / m 2 The lower limit of the oxygen permeability is, for example, 0.01 cc / m 2 / 24hr / atm may also be used. The oxygen permeability is measured under conditions of 23°C and 90% RH in accordance with JIS K7126.

[0232] The water vapor permeability of the barrier laminate of the present disclosure, such as the barrier paper, is 20 g / m 2 / 24hr or less is preferable, 10g / m 2 / 24hr or less is more preferable, 5g / m 2 / 24hr or less is more preferable, and 1.5g / m 2 The lower limit of the water vapor permeability is, for example, 0.01 g / m 2 The water vapor transmission rate is measured in accordance with JIS K7129 under conditions of 40°C and 90% RH.

[0233] The barrier laminate of the present disclosure can be suitably used for packaging material applications such as packaging bags, etc. As described above, the barrier laminate of the present disclosure has excellent interlayer adhesion and is inhibited from causing delamination, and therefore, in a packaging material including the barrier laminate, the occurrence of so-called delamination during use, etc. is inhibited.

[0234] The packaging material of the present disclosure includes the barrier laminate of the present disclosure. The packaging material of the present disclosure may further include layers having various functions in addition to the barrier laminate, as necessary.

[0235] For example, the barrier laminate can be folded in half and layered so that the base material such as a paper base material is on the outside and the heat seal layer is on the inside, and the ends or the like are heat sealed to produce a packaging material. Alternatively, a plurality of the barrier laminates can be layered so that the heat seal layers face each other, and the ends or the like are heat sealed to produce a packaging material. The entire packaging material may be composed of the barrier laminate, or only a part of the packaging material may be composed of the barrier laminate.

[0236] Examples of heat seal forms for packaging materials include side seal type, two-sided seal type, three-sided seal type, four-sided seal type, envelope seal type, hem seal type (pillow seal type), pleated seal type, flat bottom seal type, square bottom seal type, and gusset type. Self-supporting packaging bags (stand-up pouches) are also possible. Examples of heat seal methods include bar seal, rotary roll seal, belt seal, impulse seal, high frequency seal, and ultrasonic seal.

[0237] The contents to be filled in the packaging material include, for example, liquids, powders, and gels, and may be food or non-food. After the contents are filled in the packaging material, the opening of the packaging material is heat-sealed to obtain a package.

[0238] Specific contents include coffee beans, tea leaves; foods such as cheese, snacks, rice crackers, fresh and semi-fresh sweets, nuts, vegetables, fruit, fish and meat products, paste products, dried fish, smoked foods, tsukudani (food boiled in soy sauce), raw rice, cooked rice, rice cakes, baby foods, jams, mayonnaise, ketchup, cooking oils, dressings, sauces, spices, dairy products, and pet food; beverages such as beer, wine, fruit juice, green tea, and coffee; pharmaceuticals; cosmetics, shampoos, conditioners, and detergents; and metal and electronic parts.

[0239] [Method of manufacturing the barrier laminate] The barrier laminate of the present disclosure can be obtained, for example, by the transfer method described below. The method for producing a barrier laminate by the transfer method includes the steps of: A process for preparing a transfer object such as a paper member having a paper base material and a transfer film of the present disclosure (hereinafter also referred to as a "preparation process"); a step of bonding the transfer film and the transferee with the support substrate of the transfer film facing outward and the inorganic vapor deposition film facing inward (toward the transferee) via an adhesive layer to obtain an intermediate laminate (hereinafter also referred to as the "bonding step"); A step of peeling the support substrate from the heat seal layer of the intermediate laminate (hereinafter also referred to as the "peeling step"); Equipped with.

[0240] FIG. 5 is a process diagram showing an example of a method for producing a barrier laminate according to the present disclosure.

[0241] By the above-mentioned pasting step and peeling step, a transfer layer having an inorganic vapor deposition film and a heat seal layer in this order in the thickness direction can be transferred onto a transferee such as a paper member. The inorganic vapor deposition film transferred onto the paper substrate by the transfer method is less contaminated, has higher adhesion between the inorganic vapor deposition film and the adhesive layer, is homogeneous and stable, and has excellent gas barrier properties, compared to an inorganic vapor deposition film formed directly on the paper substrate by vapor deposition.

[0242] The manufacturing method of the present disclosure makes it possible to provide an inorganic vapor deposition film on a paper substrate in the same manner as when a resin substrate is used, thereby producing an environmentally friendly barrier paper that has excellent gas barrier properties.

[0243] In addition, for example, in a method in which an inorganic vapor deposition film is formed on a paper substrate and then a heat seal layer coating liquid is applied onto the inorganic vapor deposition film to form a heat seal layer, the gas barrier properties of the inorganic vapor deposition film may be reduced due to cracks or thermal damage of the inorganic vapor deposition film caused by tension, drying, etc., during the formation of the heat seal layer. The manufacturing method of the present disclosure can avoid such a reduction. In addition, the heat seal layer can suppress deterioration of the inorganic vapor deposition film during attachment in the attachment step and during peeling of the support substrate in the peeling step.

[0244] The manufacturing method of the present disclosure can thus suppress deterioration of the inorganic vapor deposition film, and therefore, for example, when the barrier laminate is used as a packaging material, the degree of deterioration due to bending, folding, and heat seal damage can be reduced.

[0245] It should be noted that although the barrier paper (hereinafter also referred to as "reference barrier paper") has a different layer structure from the barrier paper of the present disclosure, the reference barrier paper may have a layer structure of paper base material / adhesive layer / inorganic vapor deposition film / peeling layer / optional primer layer / heat seal layer.

[0246] An example of a method for producing the reference barrier paper is a method in which a paper substrate and a transfer film comprising a transfer substrate, a release layer, and an inorganic vapor deposition film are bonded together via an adhesive layer to form a laminate (1) having a layer structure of paper substrate / adhesive layer / inorganic vapor deposition film / release layer / transfer substrate, the transfer substrate is peeled off from the laminate (1) to form a laminate (2) having a layer structure of paper substrate / adhesive layer / inorganic vapor deposition film / release layer, and a primer layer and a heat seal layer are formed, as necessary, on the release layer of the laminate (2) to obtain the reference barrier paper. Hereinafter, this production method is also referred to as the "reference transfer method".

[0247] The reference transfer method has the advantages that an inorganic vapor deposition film transferred onto a paper substrate by the transfer method is less contaminated, has stronger adhesion between the inorganic vapor deposition film and the adhesive layer, is homogeneous and stable, and has better gas barrier properties than an inorganic vapor deposition film formed directly by vapor deposition on the paper substrate.

[0248] However, since the reference barrier paper has a release layer between the heat seal layer and the inorganic vapor deposition film, the adhesive strength between these layers may not be sufficient. Also, in the reference transfer method, after peeling off the transfer substrate, it is necessary to separately form a heat seal layer (heat sealable sealant layer) required, for example, when producing a packaging material, on the release layer, which increases the number of manufacturing steps.

[0249] In contrast, the barrier paper of the present disclosure does not have a release layer between the heat seal layer and the inorganic vapor deposition film, and therefore the adhesive strength between these layers is sufficiently high. Furthermore, in the manufacturing method of the present disclosure, the heat seal layer also serves as a release layer from the supporting substrate, and therefore there is no need to separately form a heat seal layer (heat sealable sealant layer) after peeling off the supporting substrate, which reduces the number of manufacturing steps.

[0250] In one embodiment of the manufacturing method of the present disclosure, the heat seal layer and the inorganic vapor deposition film are formed in advance on a thin supporting substrate. In the manufacture of the transfer film, it is possible to process it in a wider and longer length than a paper substrate, so the cost per unit area of ​​the barrier paper can be reduced.

[0251] As described above, while both the reference barrier paper and the reference transfer method have excellent advantages, the barrier paper and manufacturing method thereof disclosed herein are even better in the above-mentioned respects and provide advantageous effects.

[0252] <Preparation process> In the preparation step, a transfer medium such as a paper member and a transfer film are prepared.

[0253] The transfer medium may be, for example, a paper member. The paper member includes a paper substrate. The paper member may be a single sheet or a continuous sheet wound in a roll.

[0254] The paper member may include only a paper base material, or may include a paper base material and a printed layer provided on the paper base material. The paper member preferably includes a printed layer on the surface opposite to the surface on which the adhesive layer of the paper base material is provided. In the preparation step, the paper member may be prepared by forming a printed layer on the paper base material, or a paper member on which a printed layer is provided in advance on the paper base material may be used. The printed layer may be formed between the pasting step and the peeling step, or after the peeling step, but from the viewpoint of suppressing a decrease in gas barrier properties, it is preferable to form the printed layer before the pasting step.

[0255] The paper substrate may comprise only a paper material, or may comprise a paper material and a filler layer or a resin layer formed on the paper material. By using a paper substrate having a filler layer or a resin layer on the paper material, it is possible to suppress the adhesive from penetrating into the paper material and stabilize the adhesive strength of the adhesive layer. In the preparation step, a filler layer or a resin layer may be formed on the paper material to prepare the paper substrate, or a paper substrate having a filler layer or a resin layer formed on the paper material in advance, such as coated paper, may be used.

[0256] In addition to the formation of the above-mentioned printing layer, the paper base material may be decorated on the surface opposite to the surface on which the adhesive layer is provided, for example, by foil stamping, embossing, and shaping. The paper member thus obtained may be used. Decoration may be performed between the pasting step and the peeling step, or after the peeling step, but from the viewpoint of suppressing the deterioration of the gas barrier property, it is preferable to perform decoration before the pasting step. The details of each element are as described above, and will not be described here.

[0257] The transfer target may be a resin film as described above as a supporting substrate, or a substrate that is difficult to deposit directly (such as wood).

[0258] In the preparation step, a transfer film of the present disclosure that has been fabricated in advance is prepared.

[0259] <Attachment process> In the attachment step, a transfer film is attached to a recipient such as a paper member via an adhesive layer, with the support substrate of the transfer film facing outward and the inorganic vapor deposition film facing inward (toward the recipient) to obtain an intermediate laminate (see Figs. 5(A) and (B)). In one embodiment, by providing an adhesive layer between the paper substrate and the inorganic vapor deposition film, the inorganic vapor deposition film can be stably attached even when the surface of the paper substrate is rough.

[0260] In the attachment process, the adhesive layer may be formed on either the recipient or the transfer film, or on both, and adhesive may be supplied between the recipient and the transfer film to simultaneously form the adhesive layer and adhere the recipient and the transfer film.

[0261] In one embodiment, in the pasting step, an adhesive layer is formed on the transfer-receiving body, and the transfer film is pasted to the adhesive layer. In one embodiment, it is preferable to form the adhesive layer on a sealing layer or a resin layer of the paper member.

[0262] In one embodiment, in the pasting step, an adhesive layer is formed on the transfer film, and the transfer-receiving body is pasted to the adhesive layer. The adhesive layer is formed on the surface of the transfer film opposite to the supporting substrate. In one embodiment, it is preferable to form the adhesive layer on the inorganic vapor deposition film of the transfer film.

[0263] In one embodiment, in the bonding step, an adhesive layer is formed on the transfer recipient, an adhesive layer is formed on the transfer film, and the transfer recipient and the transfer film are bonded together so that their adhesive layers are in contact with each other.

[0264] Specific examples of methods for forming an adhesive layer include a method of forming a coating layer by coating a liquid adhesive composition, a dry lamination method using a dry lamination adhesive, and a non-solvent lamination method using a non-solvent adhesive.

[0265] Prior to forming the adhesive layer, an anchor coat layer may be formed, and then the adhesive layer may be formed to improve the adhesion of the adhesive layer. The anchor coat agent is preferably formed by coating and drying.

[0266] The pasting step can be carried out by a general known device, temperature and pressure depending on the type and characteristics of the adhesive and the method for forming the adhesive layer. For example, when forming the adhesive layer by the dry lamination method, in one embodiment, a dry lamination adhesive is applied and dried on the transferee and / or transfer film to form an adhesive layer, and the transferee and the transfer film are superposed with the adhesive layer interposed therebetween, and then pressed to obtain an intermediate laminate. Heating may be performed as necessary.

[0267] The method and pressure of pressing the intermediate laminate in the bonding step are preferably selected and set so as to minimize damage to the inorganic vapor deposition film. The pressure during pressing is preferably 0.1 MPa or more and 10 MPa or less. For example, the adhesive layer may be softened by heating before bonding. Depending on the composition of the adhesive, the adhesive layer may be cured by heating after bonding.

[0268] <Peeling process> In the peeling step, the support substrate is peeled from the heat seal layer of the intermediate laminate (see FIG. 5(C)). For example, after sufficient adhesive strength is developed by the adhesive layer between the transfer object and the transfer film, the support substrate is peeled from the intermediate laminate. Peeling can be performed using known equipment and at known temperatures depending on the type and characteristics of the adhesive layer and the method for forming the adhesive layer.

[0269] In one embodiment, the support substrate of the transfer film may be peeled off while the transfer receiving body and the transfer film are attached to each other via the adhesive layer. In this manner, a barrier laminate such as a barrier paper of the present disclosure is obtained.

[0270] For example, when the intermediate laminate is a continuous sheet wound into a roll, the supporting substrate may be continuously peeled off from the heat seal layer of the intermediate laminate using a release roll, and the barrier laminate and the supporting substrate may each be wound up.

[0271] The present disclosure relates to, for example, the following [1] to

[19] . [1] A transfer film comprising a supporting substrate, a heat seal layer, and an inorganic vapor deposition film in that order in the thickness direction, wherein the inorganic vapor deposition film and the heat seal layer are in contact with each other, or the transfer film further comprises an anchor coat layer between the inorganic vapor deposition film and the heat seal layer, and the inorganic vapor deposition film and the anchor coat layer are in contact with each other. [2] The transfer film according to [1] above, wherein the inorganic vapor deposition film is formed directly on one side of the heat seal layer by vapor deposition. [3] The transfer film according to [1] above, wherein the inorganic vapor deposition film is formed directly on one side of the anchor coat layer by vapor deposition. [4] The transfer film according to any one of the above [1] to [3], further comprising a protective layer on the inorganic vapor deposition film. [5] The transfer film according to any one of the above [1] to [4], wherein the inorganic vapor deposition film contains at least one selected from aluminum, aluminum oxide, and silicon oxide. [6] The transfer film described in any one of [1] to [5] above, wherein the heat seal layer has an indentation hardness of 0.15 GPa or less by a nanoindentation method and a composite elastic modulus of 2.0 GPa or less. [7] The transfer film described in any one of [1] to [6], wherein the transition point of the anchor coat layer, as measured by local thermal analysis using a thermal probe, is 90°C or higher and 140°C or lower. [8] NO in the anchor coat layer measured while etching the transfer film using time-of-flight secondary ion mass spectrometry (TOF-SIMS). 2 - The transfer film according to any one of the above [1] to [7], having a normalized ion intensity of 3.0 or more and 4.2 or less. [The normalized intensity is the NO intensity measured by TOF-SIMS. 2 - The detection intensity of ions is expressed as CN - The NO concentration was normalized by dividing the NO concentration by the detection intensity and multiplying by 100,000. 2 -It means the common logarithm of the average detection intensity after normalization of the ion.] [9] A barrier laminate comprising a substrate, an adhesive layer, an inorganic vapor deposition film, and a heat seal layer in this order in the thickness direction, wherein the inorganic vapor deposition film and the heat seal layer are in contact with each other, or the barrier laminate further comprises an anchor coat layer between the inorganic vapor deposition film and the heat seal layer, and the inorganic vapor deposition film and the anchor coat layer are in contact with each other.

[10] The barrier laminate according to [9] above, wherein the inorganic vapor deposition film is formed directly on one side of the heat seal layer by vapor deposition.

[11] The barrier laminate according to [9] above, wherein the inorganic vapor deposition film is formed directly on one surface of the anchor coat layer by vapor deposition.

[12] A barrier laminate comprising a substrate, an adhesive layer, an inorganic vapor deposition film, and a heat seal layer in this order in the thickness direction, the barrier laminate not comprising a release layer between the inorganic vapor deposition film and the heat seal layer.

[13] The barrier laminate according to

[12] , further comprising an anchor coat layer between the inorganic vapor deposition film and the heat seal layer.

[14] The barrier laminate according to any one of the above [9] to

[13] , wherein the inorganic vapor deposition film contains at least one selected from aluminum, aluminum oxide, and silicon oxide.

[15] The barrier laminate according to any one of the above [9] to

[14] , wherein the substrate is a paper substrate.

[16] The barrier laminate according to

[15] , wherein the paper base material comprises a paper material and a sealing layer or a resin layer formed on the surface of the paper material facing the adhesive layer.

[17] A barrier laminate comprising a paper base material, an adhesive layer, an inorganic vapor deposition film, and a heat seal layer in this order in the thickness direction, wherein the inorganic vapor deposition film and the heat seal layer are in contact with each other, or the barrier laminate further comprises an anchor coat layer between the inorganic vapor deposition film and the heat seal layer, and the inorganic vapor deposition film and the anchor coat layer are in contact with each other, the paper base material is made of a paper material, and does not comprise a sealing layer, a resin layer, or a clay coat layer.

[18] The barrier laminate according to any one of the above [9] to

[17] , further comprising a printed layer on a surface of the substrate opposite to the adhesive layer side.

[19] The barrier laminate according to any one of the above [9] to

[18] , wherein the adhesive layer has a thickness of 0.5 μm or more and 20 μm or less. EXAMPLES

[0272] The transfer film and barrier laminate of the present disclosure will be described in more detail with reference to the following examples, but the transfer film and barrier laminate of the present disclosure are not limited to these examples.

[0273] The main products used in the examples are as follows: [Paper substrate] Paper base material A: Ryuo Coat, single-fed sheet, manufactured by Daio Paper Co., Ltd. Basis weight 55g / m 2 , single-sided coated product. Paper base material B: Ryuo Coat, single-fed sheet, manufactured by Daio Paper Co., Ltd. Basis weight 80g / m 2 , single-sided coated product. Paper base material C: Daio Paper Co., Ltd., Nagoya Sararyuo, sheet-fed sheet, Basis weight 50g / m 2 , Single-glazed item.

[0274] [Adhesive] Adhesive A: Dry lamination adhesive manufactured by Rock Paint Co., Ltd. RU-40 / H-1=15 / 2 mass ratio, When in use, it is attached using the dry lamination method. Adhesive B: Dry lamination adhesive manufactured by Rock Paint Co., Ltd. RU-77T / H-7=10 / 1 mass ratio, When in use, it is attached using the dry lamination method.

[0275] [Example] [Example 1A: Production of Transfer Film A] A heat seal layer coating solution having the following composition was applied to the non-corona treated surface of a PET film (manufactured by Toyobo Co., Ltd., thickness 12 μm, one-sided corona treated product) by gravure coating and dried to form a heat seal layer with a thickness of 5 μm. A polyester (manufactured by Toyobo Co., Ltd., product name: Vylon (registered trademark) UR1700) as a base agent, an XDI-based isocyanate (manufactured by Mitsui Chemicals Co., Ltd., product name: Takenate D110N) as a curing agent, and nitrocellulose as an additive were mixed in a ratio of base agent:curing agent:nitrocellulose (solid content mass ratio) = 1:1:1 to prepare an anchor coat agent. The anchor coat agent was applied to the heat seal layer by gravure coating and dried to form an anchor coat layer with a thickness of 500 nm. An aluminum vapor deposition film with a thickness of 45 nm was formed as an inorganic vapor deposition film on the anchor coat layer by physical vapor deposition. A protective layer coating solution containing a urethane resin and a silane coupling agent was applied onto the aluminum deposition film by gravure coating and dried to form a protective layer with a thickness of 750 nm. In this way, a transfer film A having a layer structure of PET film / heat seal layer / anchor coat layer / aluminum deposition film / protective layer was obtained.

[0276] (Coating Liquid for Heat Seal Layer) Chemipearl (registered trademark) S120 (Mitsui Chemicals, Inc., water-based ionomer emulsion, composition: metal salt of ethylene-methacrylic acid copolymer, self-emulsifying emulsion)

[0277] [Example 1B: Production of Transfer Film B] Transfer film B was obtained in the same manner as transfer film A, except that a 20 nm thick aluminum oxide vapor deposition film was formed as the inorganic vapor deposition film, and the layer structure was PET film / heat seal layer / anchor coat layer / aluminum oxide vapor deposition film / protective layer.

[0278] [Example 1C: Production of Transfer Film C] Transfer film C, which has a layer structure of PET film / heat seal layer / anchor coat layer / silicon oxide vapor deposition film / protective layer, was obtained in the same manner as transfer film A, except that a 35 nm thick silicon oxide vapor deposition film was formed as the inorganic vapor deposition film by physical vapor deposition.

[0279] [Example 1] Adhesive A is applied to the coated surface of paper base material A (A4 size), with a dry basis weight of 3.0 g / m 2 and dried to form an adhesive A layer.

[0280] The adhesive A layer surface of the paper base material A was placed opposite the protective layer surface of the transfer film A (A4 size), and the two were bonded together, pressurized at 0.5 MPa, and then aged for 3 days at 40° C. In this way, an intermediate laminate having a layer structure of paper base material A [paper material / coating layer] / adhesive A layer / protective layer / aluminum vapor deposition film / anchor coating layer / heat seal layer / PET film was obtained. The PET film in the intermediate laminate was peeled off to obtain a barrier paper.

[0281] [Examples 2 - 6] Barrier paper was obtained in the same manner as in Example 1, except that the type of paper substrate, the type of adhesive, and the transfer film were changed as described in Table 1.

[0282] [Reference Example] [Reference Example 1A: Production of Reference Transfer Film A] A diluted release agent solution (a mixture of release agent k-45-3 and ethyl acetate, manufactured by Showa Ink Co., Ltd., in a mass ratio of 1:1) was applied to the corona-treated surface of a PET film (manufactured by Toyobo Co., Ltd., thickness 12 μm, corona-treated on one side) until the basis weight after drying was 1.0 g / m 2The coating was applied by a bar coating method so that the thickness of the coating was 100 nm, and the coating was dried in an oven at 80° C. for 1 minute to form a release layer, thereby obtaining a release substrate having a PET film and a release layer. On the release layer, an aluminum vapor deposition film having a thickness of 45 nm was formed as an inorganic vapor deposition film by a physical vapor deposition method. On the aluminum vapor deposition film, a protective layer coating liquid containing a urethane resin and a silane coupling agent was applied by a gravure coating method and dried to form a protective layer having a thickness of 750 nm. In this way, a reference transfer film A having a layer structure of PET film / release layer / aluminum vapor deposition film / protective layer was obtained.

[0283] [Reference Example 1B: Production of Reference Transfer Film B] Reference transfer film B, having a layer structure of PET film / release layer / aluminum oxide vapor deposition film / protective layer, was obtained in the same manner as reference transfer film A, except that a 20 nm thick aluminum oxide vapor deposition film was formed as the inorganic vapor deposition film.

[0284] [Reference Example 1C: Production of Reference Transfer Film C] Reference transfer film C, which has a layer structure of PET film / release layer / silicon oxide vapor deposition film / protective layer, was obtained in the same manner as reference transfer film A, except that a 35 nm thick silicon oxide vapor deposition film was formed as the inorganic vapor deposition film by physical vapor deposition.

[0285] [Reference Example 1] Adhesive A is applied to the coated surface of paper base material A (A4 size), with a dry basis weight of 3.0 g / m 2 The adhesive A layer was formed by applying and drying so that the adhesive A layer surface of the paper substrate A and the protective layer surface of the reference transfer film A (A4 size) were placed opposite each other, and the two were laminated together, pressurized at 0.5 MPa, and then aged at 40°C for 3 days. In this way, a laminate having a layer structure of the paper substrate A [paper material / coating layer] / adhesive A layer / protective layer / aluminum vapor deposition film / peeling layer / PET film was obtained.

[0286] The PET film in the laminate was peeled off, and the primer layer coating liquid was applied and dried on the peeling layer to form a primer layer. The heat seal layer coating liquid having the above composition was applied and dried on the primer layer to form a heat seal layer having a thickness of 5 μm. In this manner, a reference barrier paper was obtained.

[0287] [Reference Examples 2 - 6] A reference barrier paper was obtained in the same manner as in Reference Example 1, except that the type of paper substrate, the type of adhesive, and the reference transfer film were changed as described in Table 2.

[0288] [Evaluation 1] [Adhesion] A two-component curing polyurethane adhesive was applied to a 70μm thick unstretched polypropylene film, which was then dried and then dry laminated with a 15μm thick stretched nylon film to obtain a laminated film. A two-component curing polyurethane adhesive was applied to the heat seal layer side of the barrier paper or reference barrier paper, which was then dried and then dry laminated with the above laminated film to obtain a laminated composite film.

[0289] The laminated composite film was aged for 48 hours, and then cut into 15 mm-wide strips to obtain test pieces. The adhesion strength (peel strength) of the test pieces was measured using a tensile tester (manufactured by Orientec Co., Ltd. [model name: Tensilon universal material testing machine]) in accordance with JIS K6854-2.

[0290] For the measurement, the polypropylene film side and the (reference) barrier paper side, which had been peeled off beforehand for the measurement, were each held with the measuring device's gripping tools and pulled in opposite directions (180° peeling: T-peel method) perpendicular to the surface direction of the part where the polypropylene film and the (reference) barrier paper are still laminated, at a speed of 50 mm / min, and the average tensile stress in the stable region was measured to obtain the adhesion strength (N / 15 mm).The (reference) barrier paper was evaluated according to the following evaluation criteria.

[0291] [Evaluation Criteria] ·AA: High adhesion strength, suitable for practical applications such as packaging materials. BB: Medium adhesion strength, There is no problem with application to practical uses such as packaging materials. CC: Very low adhesion strength, It is difficult to apply this to practical applications such as packaging materials.

[0292] [Table 1]

[0293] [Table 2]

[0294] The barrier paper obtained in the examples did not have a release layer between the inorganic vapor deposition film and the heat seal layer, and therefore showed better interlayer adhesion compared to the reference barrier paper which had a release layer between the inorganic vapor deposition film and the heat seal layer.

[0295] [Test Example 1A] A transfer film having a layer structure of PET film / heat seal layer / anchor coat layer / aluminum vapor deposition film (40 nm thick) / protective layer was obtained using the same procedure as in Example 1A. Using this transfer film, a barrier paper having a layer structure of heat seal layer / anchor coat layer / aluminum vapor deposition film (40 nm thick) / protective layer / adhesive layer / paper (general paper) was obtained using a procedure similar to that of Example 1.

[0296] [Test Example 2A] A reference transfer film having a layer structure of PET film / polyester-based release layer / anchor coat layer / aluminum vapor deposition film (thickness 40 nm) / protective layer, and a reference barrier paper having a layer structure of polyester-based release layer / anchor coat layer / aluminum vapor deposition film (thickness 40 nm) / protective layer / adhesive layer / paper (general paper) were obtained in the same manner as in Test Example 1A, except that a release layer was formed using a polyester-based release agent instead of using Chemipearl (registered trademark) S120 to form a heat seal layer.

[0297] [Test Example 3A] A reference transfer film having a layer structure of PET film / polycarbonate-based release layer / anchor coat layer / aluminum vapor deposition film (thickness 40 nm) / protective layer, and a reference barrier paper having a layer structure of polycarbonate-based release layer / anchor coat layer / aluminum vapor deposition film (thickness 40 nm) / protective layer / adhesive layer / paper (general paper) were obtained in the same manner as in Test Example 1A, except that a release layer was formed using a polycarbonate-based release agent instead of using Chemipearl (registered trademark) S120 to form a heat seal layer.

[0298] [Evaluation 2] [Measurement of Indentation Hardness and Composite Elastic Modulus] For the transfer film of Test Example 1A and the reference transfer films of Test Examples 2A to 3A, the indentation hardness (H IT ) and composite elastic modulus (E r The indentation hardness H IT and composite elastic modulus E r Each was recorded as the arithmetic mean value of the values ​​measured at 10 points with good reproducibility.

[0299] The measurement conditions were as follows: the indentation depth control method (indentation depth 100 nm constant, loading 10 seconds / holding 5 seconds / unloading 10 seconds). The indentation depth was pressed into the heat seal layer or peeling layer from the cross section of the heat seal layer or peeling layer for 10 seconds to a depth of 100 nm, and the indentation depth was held for 5 seconds. The indentation depth was then removed for 10 seconds. This resulted in the maximum load P max , contact projection area A at maximum depth p and load-displacement curves were obtained, and the indentation hardness and composite modulus were calculated from the obtained load-displacement curves. The measurements were carried out in a room temperature (23°C) environment. The indenter was pressed into the heat seal layer or peel layer at a location near the center in the thickness direction of the heat seal layer or peel layer, among the exposed cross sections of the heat seal layer or peel layer. The cross section was obtained by cutting the transfer film (for reference) in the thickness direction perpendicular to the main surface. The cross section was prepared by preparing a block in which the transfer film (for reference) was embedded in an embedding resin, and cutting the block using a commercially available rotary microtome in a room temperature (23°C) environment. Finishing was carried out with a diamond knife. The thickness of each layer can also be measured by observing the cross section.

[0300] [Gas Barrier Property Evaluation] The barrier paper of Test Example 1A or the reference barrier paper of Test Examples 2A to 3A was cut out to obtain a test piece. The oxygen permeability (cc / m 2 / 24hr / atm and water vapor permeability (g / m 2 / 24hr) was measured by the following method. In addition, (for reference) these physical properties were also measured for a test piece in which the barrier paper was folded in four and then returned to its original shape.

[0301] Using an oxygen transmission rate measuring device (MOCON, OX-TRAN2 / 20), the test piece was set so that the paper substrate side was the oxygen supply side, and the oxygen transmission rate (OTR; unit: cc / m) was measured in accordance with JIS K7126 under an environment of 23°C and 90% RH. 2OTR was measured at 1.5 or less and rated as AA, OTR between 1.5 and 3.0 or less and rated as BB, and OTR over 3.0 was rated as CC.

[0302] Using a water vapor transmission rate measuring device (MOCON, PERMATRAN-w 3 / 33), the paper substrate side of the test piece was set so that it was the water vapor supply side, and the water vapor transmission rate (WVTR; unit: g / m) was measured in accordance with JIS K7129 under an environment of 40°C and 90% RH. 2 WVTR was measured using a time course averaging (WVTR) of 1.5 or less, 1.5 or more and 5.0 or less, and 1.5 or more and 5.0 or less, respectively, and 1.5 or more and 5.0 or more and 5.0 or more, respectively, were evaluated as AA, BB, and CC, respectively.

[0303] [Table 3]

[0304] [Test Example 1B] A transfer film having a layer structure of PET film / heat seal layer / anchor coat layer / silicon oxide vapor deposition film / protective layer was obtained in the same manner as in Example 1C, except that the content of nitrocellulose in the anchor coat agent was changed to 0 parts by mass per 100 parts by mass of the total amount of the base agent and the curing agent.

[0305] [Test Examples 2B - 4B] A transfer film was obtained in the same manner as in Test Example 1B, except that in the anchor coating agent, the nitrocellulose content was changed to 5 parts by mass (Test Example 2B), 50 parts by mass (Test Example 3B), and 200 parts by mass (Test Example 4B) per 100 parts by mass of the total amount of the base agent and hardener.

[0306] [Evaluation 3] [Measurement of Transition Point] In the same manner as in the above <Measurement of indentation hardness and composite elastic modulus>, a block was prepared by embedding the transfer film in embedding resin, and the block was cut at room temperature (23°C) using a commercially available rotary microtome to prepare a cross section of the transfer film. Finishing was performed with a diamond knife.

[0307] The measurement device used was a nanoTA manufactured by ANASYS INSTRUMENTS, and the thermal probe used was a PR-EX-AN2-300-5 manufactured by ANASYS INSTRUMENTS.

[0308] Before the measurement, the following calibration was performed. NanoTA Calibration Samples manufactured by BRUKER were prepared as standard samples. The standard sample stages contained polycaprolactone (softening point: 55°C), polyethylene (softening point: 116°C), and polyethylene terephthalate (softening point: 235°C), all of which have known softening points. Each standard sample was heated while being brought into contact with a thermal probe on its surface. During heating, the thermal expansion directly below the thermal probe was measured, and a graph was obtained showing the deflection versus voltage. The measurement conditions set on the device were as follows: Measurement start temperature: 0.1V Measurement end temperature: 10V Heating rate: 0.2V / sec

[0309] Using the softening point of each standard sample, the graph showing the displacement of the thermal probe versus potential was converted into a graph showing the displacement versus temperature. In this manner, calibration was performed.

[0310] After the calibration, the transition point of the anchor coat layer was measured. The measurement point of the transition point was near the center in the thickness direction of the anchor coat layer among the exposed cross-sections of the anchor coat layer. Measurements were performed at five or more points on the same cross-section, and the transition point was recorded as the arithmetic average of the values ​​of the five points that were measured with good reproducibility.

[0311] The measurement was performed by bringing a thermal probe into contact with the cross section of the anchor coat layer, heating the cross section under the conditions described below while the thermal probe was in contact, and obtaining a graph (thermal expansion curve) showing the displacement of the thermal probe versus temperature. Measurement start temperature: 40℃ End of measurement temperature: 350℃ Heating rate: 5℃ / sec

[0312] In the obtained thermal expansion curve, the transition point appearing on the lowest temperature side was obtained. When a peak was obtained in the thermal expansion curve, the temperature at the peak of the thermal expansion curve was taken as the transition point. A thermal expansion curve in which a continuous displacement drop of 0.2 V or more was measured from the maximum displacement in the thermal expansion curve was considered to have a peak.

[0313] However, if no peak is observed in the thermal expansion curve but a "shoulder peak" is observed, or if a "shoulder peak" is observed at a temperature lower than the temperature at which a peak is obtained, the temperature of the "shoulder peak" is taken as the transition point. A "shoulder peak" is defined as a point where the slope of the thermal expansion curve (displacement / temperature) changes and the slope of the thermal expansion curve becomes small, approaching zero, even though it is not a clearly convex shape. Specifically, the absolute value of the slope (=slope) of the tangent on the lower temperature side where the slope of the thermal expansion curve changes is taken as the transition point. A ) and the absolute value of the slope of the tangent line on the higher temperature side where the slope of the thermal expansion curve changes (=slope B ) but (slope A )>{(slope B )×5} relationship and (slope B ) ≦ 0.02V / ℃, the thermal expansion curve was deemed to have a "shoulder peak". The tangent was drawn where the thermal expansion curve was relatively stable and close to a straight line. For thermal expansion curves deemed to have a "shoulder peak", the transition point was the temperature at the intersection of the tangents drawn before and after the slope of the thermal expansion curve changed.

[0314] [TOF - SIMS Measurement] NO in the anchor coat layer 2 -The normalized intensity of the ions was measured using time-of-flight secondary ion mass spectrometry (TOF-SIMS). Specifically, a time-of-flight secondary ion mass spectrometer (ION TOF, TOF.SIMS5) was used to perform mass analysis of various ions in each layer while repeatedly soft etching at a constant speed from the protective layer surface of the transfer film to the PET film side with a Cs (cesium) ion gun. In the anchor coat layer, CN derived from the resin component - ion (mass number 26.002) and NO derived from nitrocellulose 2 - Mass analysis of the ion (mass number 45.992) was performed.

[0315] The specific TOF-SIMS measurement conditions are as follows: Primary ion type: Bi 3 ++ (0.2pA, 100μs) ·Measurement area: 150×150μm 2 Etching gun type: Cs (1keV, 60nA) Etching area: 600×600μm 2 Etching rate: 10sec / cycle Vacuum time: 1×10 -6 >15 hours at <mbar The TOF-SIMS measurements were performed within 30 hours after the start of evacuation.

[0316] Figure 6 shows the CN - An example of TOF-SIMS measurement before normalization based on the detection intensity of ions is shown in FIG. - Ion, NO 2 - ions and SiO 2 The vertical axis of the graph (intensity) indicates the intensity of the detected ions, and the horizontal axis (s) indicates the etching time.

[0317] [Gas Barrier Property Evaluation] Using the transfer films of Test Examples 1B to 4B, barrier paper having a layer structure of heat seal layer / anchor coat layer / silicon oxide vapor deposition film / protective layer / adhesive layer / paper (general paper) was obtained in a similar manner to Example 1. The barrier paper was cut out to obtain a test piece. Using this test piece, the oxygen permeability (cc / m 2 / 24hr / atm and water vapor permeability (g / m 2 / 24hr) was measured in the same manner as above.

[0318] An OTR of 1.5 or less was rated as AA, an OTR of more than 1.5 and less than 3.0 was rated as BB, and an OTR of more than 3.0 was rated as CC. WVTR of 0.6 or less was rated as SSS, WVTR of more than 0.6 and less than 1.0 was rated as SS, and WVTR of more than 1.0 was rated as S.

[0319] [Appearance Evaluation] The appearance of the anchor coat layer upon formation was evaluated visually. ·AA: Good BB: Partial blocking marks CC: Partially peeled off

[0320] [Table 4]

[0321] The barrier papers of Test Examples 1B, 2B, and 4B had WVTR and OTR that were acceptable for practical use. The barrier paper of Test Example 3B had even better WVTR and OTR than the barrier papers of Test Examples 1B, 2B, and 4B. The anchor coat layers of Test Examples 1B, 2B, and 4B had an appearance that was acceptable for practical use. The anchor coat layer of Test Example 3B had an even better appearance than the anchor coat layers of Test Examples 1B, 2B, and 4B.

[0322] As will be understood by those skilled in the art, the transfer film and barrier laminate of the present disclosure are not limited by the description of the above examples, the above examples and specification are merely intended to explain the principles of the present disclosure, and various modifications or improvements can be made without departing from the spirit and scope of the present disclosure, and all of these modifications or improvements are included within the scope of the present disclosure that is claimed for protection. Furthermore, the scope of protection claimed by the present disclosure includes not only the description of the claims but also equivalents thereof. [Explanation of symbols]

[0323] 1. Barrier laminate 2. Transfer film 10...Base material 12...printing layer 20...Adhesive layer 30...Inorganic vapor deposition film 32 Anchor coat layer 40...Heat seal layer 50 Supporting substrate (transfer substrate)

Claims

1. A supporting substrate; A heat seal layer; Inorganic deposition film and A transfer film having the following in this order in a thickness direction: The inorganic vapor deposition film and the heat seal layer are in contact with each other, or The transfer film further includes an anchor coat layer between the inorganic vapor deposition film and the heat seal layer, and the inorganic vapor deposition film and the anchor coat layer are in contact with each other. Transfer film.

2. The transfer film according to claim 1 , wherein the inorganic vapor deposition film is formed directly on one surface of the heat seal layer by vapor deposition.

3. The transfer film according to claim 1 , wherein the inorganic vapor deposition film is formed directly on one surface of the anchor coat layer by vapor deposition.

4. The transfer film according to any one of claims 1 to 3, further comprising a protective layer on the inorganic vapor deposition film.

5. The transfer film according to any one of claims 1 to 4, wherein the inorganic vapor deposition film contains at least one selected from the group consisting of aluminum, aluminum oxide, and silicon oxide.

6. The transfer film according to any one of claims 1 to 5, wherein the heat seal layer has an indentation hardness of 0.15 GPa or less as measured by a nanoindentation method and a composite elastic modulus of 2.0 GPa or less.

7. The transfer film according to any one of claims 1 to 6, wherein the transition point of the anchor coat layer, as measured by local thermal analysis using a thermal probe, is 90°C or higher and 140°C or lower.

8. The NO in the anchor coat layer was measured while etching the transfer film using time-of-flight secondary ion mass spectrometry (TOF-SIMS). 2 - The transfer film according to any one of claims 1 to 7, wherein the normalized ion intensity is 3.0 or more and 4.2 or less. [The normalized intensity is the NO intensity measured by TOF-SIMS. 2 - The detection intensity of the ion is CN - The NO concentration was normalized by dividing the NO concentration by the detection intensity and multiplying by 100,000. 2 - It means the common logarithm value of the average value of the normalized detection intensity of the ion.]

Citation Information

Patent Citations

  • Ptp packing cover material and production thereof

    JP1995096968A

  • Manufacturing method for transfer metal-deposited sheet material, and transfer metal-deposited sheet material

    JP2003231395A

  • PTP lid, and PTP package using the same

    JP2005178829A

  • Decorative transfer foil and method for manufacturing decorative resin molding using the same

    JP2015066697A

  • Gas barrier laminates and gas barrier containers

    JP4622201B2